Electrolyte composition
By designing a non-aqueous electrolyte composition containing sodium salt and glycol dimethyl ether, the electrolyte of sodium ion battery is optimized, and the safety hazards of incomplete peeling of sodium ion batteries during anode electroplating and water reaction are solved, and high energy density and Cyclic stability reduces costs.
Patent Information
- Application Number
- CN202280096408.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-24
- Filing Date
- 2022-10-07
- Publication Date
- 2025-01-03
AI Technical Summary
During the manufacturing process, existing sodium ion batteries have problems such as incomplete electroplating and peeling of the anode, dendrites growth and reaction with water, resulting in safety hazards and high costs, and cannot compete with lithium ion batteries for weight energy density.
A non-aqueous electrolyte composition is designed, including a sodium salt and a solvent system based on glycol dimethyl ether, and the addition of appropriate amounts of sulfur, boron, nitrile, phosphorus compounds and surfactants are added to optimize the electrolyte composition to improve electrochemistry. Performance and stability.
A sodium ion battery that can be recharged at room temperature is achieved, with high energy density and cycle stability, reducing manufacturing costs, and avoiding the risks of incomplete electroplating and water reaction of the anode.
Smart Images

Figure CN119256402A_ABST
Abstract
Description
Field of the Invention
[0001] The present invention relates to a novel non-aqueous electrolyte composition, an anode-free sodium battery comprising the novel non-aqueous electrolyte composition, and an energy storage device comprising the anode-free sodium battery. The present invention also relates to a sodium ion battery comprising the novel non-aqueous electrolyte composition. Background of the Invention
[0003] Sodium-ion batteries are similar in many ways to the lithium-ion batteries commonly used today; they are both reusable secondary batteries that include an anode (negative electrode), a cathode (positive electrode), and electrolyte materials, both are capable of storing energy, and both are charged and discharged via similar reaction mechanisms. + (or Li + ) ions are deintercalated from the cathode and inserted into the anode. Simultaneously, charge-balancing electrons travel from the cathode through an external circuit containing the charger and into the anode of the battery. The same process occurs during discharge, but in the opposite direction.
[0004] Lithium-ion battery technology has gained a lot of attention in recent years and provides the preferred portable battery for most electronic devices used today. However, lithium is not a cheap source of metal and is considered too expensive for use in large-scale applications. In contrast, sodium is much more abundant than lithium, and some researchers predict that this will provide a cheaper and longer-lasting way to store energy in the future, especially for large-scale applications such as storing energy on the grid.
[0005] Sodium-ion batteries include an active material layer coated on a current collector foil to form the cathode, and a similar arrangement exists for the corresponding anode. The cathode and anode are physically separated by a separator that allows the flow of ions in a liquid electrolyte medium that is uniformly present in the battery and wets the entire cathode, anode, and separator. During charging, the Na + Ions are shuttled from the cathode active material and inserted into the anode active material (electrons flow through an external circuit), and the reverse process occurs during discharge (sodium ions are extracted from the anode active material and inserted into the cathode active material as electrons flow through an external circuit, doing useful work).
[0006] In contrast, for a "sodium battery", the anode consists of sodium metal (either as a standalone Na metal foil / sheet or as a Na metal foil / sheet laminated on another current collector foil / sheet), and the cathode, separator, and electrolyte are the same as those used in the sodium-ion batteries described above. Thus, in a "sodium battery", Na plating / stripping occurs on the Na metal foil during each charge / discharge cycle (the cathode behaves in the same way as in a sodium-ion battery).
[0007] However, as understood, using sodium metal as the anode may not be the most ideal choice, especially from a battery manufacturing perspective. Additionally, the plating and stripping processes at the anode are rarely fully reversible, and dendrite growth occurs, leading to early failure. Furthermore, sodium metal reacts violently with water, a reaction that can lead to explosions during the manufacturing stage. Therefore, using sodium metal as the anode in sodium batteries will require the use of an inert atmosphere, which is expected to significantly increase battery manufacturing costs.
[0008] Sodium-ion batteries are currently unable to compete with lithium-ion batteries in terms of gravimetric energy density. However, sodium batteries (using sodium metal as the anode, as discussed above) could potentially have higher energy density than existing commercial lithium-ion batteries, but these batteries would be more expensive to manufacture for the reasons discussed above. Thus, there remains a need to design room temperature rechargeable sodium-containing batteries that can achieve comparable or better specific energy density than existing commercial lithium-ion batteries while also being inexpensive and easy to manufacture.
[0009] WO 2018 / 151674 describes an “anode-free sodium battery”, also known as an in-situ sodium plating battery. “Anode-free sodium battery” refers to a battery in which the working principle of the anode-free sodium battery involves the extraction / insertion of sodium metal cations (Na + ) and the electroplating / stripping of sodium metal (Na) on the anode current collector. This operating principle is different from a) "sodium-ion batteries", in which the operating principle of sodium-ion batteries involves the extraction / insertion of sodium metal cations (Na) at the cathode active material. + ) and the extraction / insertion of sodium metal cations (Na + ), and b) "sodium batteries", where the operating principle of sodium batteries involves the extraction / insertion of sodium metal cations (Na + ) and electroplating / stripping of sodium metal (Na) at a sodium metal anode.
[0010] In more detail, WO 2018 / 151674 shows an "anode-free sodium battery" that uses an anode current collector that is "original" before the initial first charging cycle of the anode-free sodium battery; 1M NaBF4 in tetraethylene glycol dimethyl ether as an electrolyte; and rhombohedral Na2Fe2(CN)6 as a cathode active material. After the initial cycle, the anode-free sodium battery is able to provide a capacity of about 90mAh / g at an average discharge voltage of 3.22V, and the cycle of this battery is very stable, showing a capacity retention rate of about 76% of its initial value after 60 cycles.
[0011] US2020 / 0058222 also describes an “anode-free sodium battery”. In this disclosure, an anode-free sodium battery is shown, which uses an anode current collector comprising one or more carbon nucleation layers before the initial first charging cycle of the anode-free sodium battery; 1M NaPF6 as an electrolyte; and pre-sodiumized FeS2 as a cathode active material. This pre-sodiumization is an expensive and difficult to implement method, so the commercial practicality of this disclosure is questionable.
[0012] One area that requires more attention is the development of suitable electrolyte compositions, particularly for anode-free sodium batteries.
[0013] Although the design of suitable electrolyte compositions has received less attention than active materials (electrodes), their importance should not be overlooked as they are largely key to battery life and determining the actual performance that can be achieved by the battery, such as in terms of capacity, rate capability, safety, etc. However, to be a suitable electrolyte composition, it must meet a number of properties, which include:
[0014] Chemical stability - no significant adverse reactions during battery operation, including reactions within the electrolyte itself or with the separators, electrodes, current collectors or packaging materials used;
[0015] Electrochemical stability—there must be a wide electrochemical stability window, i.e., a large interval between the high and low onset potentials for decomposition by oxidation or reduction;
[0016] Thermal stability - the electrolyte composition must not decompose or chemically break down during normal battery operation and at operating temperatures;
[0017] Physical properties—the electrolyte composition must be a liquid, so its melting and boiling points must be well above the internal operating temperature of the battery;
[0018] High ionic conductivity and low electronic conductivity are achieved through Na + Transmits the necessary power to maintain battery operation and minimize battery self-discharge;
[0019] Low toxicity;
[0020] Based on sustainable chemistry, i.e. using abundant elements and made via low-impact synthesis (energy, pollution, etc.); and
[0021] Cost effective manufacturing.
[0022] It is therefore an object of the present invention to provide improved sodium ion conducting electrolyte compositions (i.e., they are electrolyte compositions specifically designed for use in anode-free sodium batteries). The electrolyte compositions of the present invention will be cost effective and will exhibit excellent electrochemical performance, particularly in anode-free sodium batteries. The electrolyte compositions of the present invention are also useful in sodium ion batteries. SUMMARY OF THE INVENTION
[0024] The present invention achieves these objects by providing: a non-aqueous electrolyte composition comprising: one or more sodium-containing salts; and a solvent system comprising: a first component comprising one or more glyme-based solvents; and a second component comprising (or optionally consisting essentially of) one or more additives selected from:
[0025] Sulfur-containing compounds in an amount not greater than about 10% by weight of the solvent system;
[0026] a boron-containing compound in an amount not greater than about 20% by weight of the solvent system;
[0027] · Nitrile-containing compounds in an amount not greater than about 10% of the solvent system;
[0028] a phosphorus-containing compound in an amount not greater than about 10% by weight of the solvent system;
[0029] A surfactant in an amount no greater than about 20% by weight of the solvent system; and optionally
[0030] The total amount of the one or more additives does not exceed about 20% by weight of the solvent system, and desirably does not exceed about 17.5% by weight of the solvent.
[0031] For the avoidance of any doubt, when one or more additives comprise a combination of compounds as indicated, the amounts of such compounds are applied as indicated. For example, TEL 66X is not in accordance with the present invention because it contains a sulfur-containing compound in an amount of 15% by weight of the solvent system. That is, it does not satisfy the requirement that "the amount of the sulfur-containing compound is not greater than about 10% by weight of the solvent system".
[0032] Preferably, the second component comprises (or optionally consists essentially of) one or more additives selected from the group consisting of:
[0033] Sulfur-containing compounds in an amount of no greater than about 5%, preferably no greater than about 3%, and very preferably no greater than about 2.5% by weight of the solvent system;
[0034] a boron-containing compound in an amount no greater than about 15 wt %, preferably no greater than about 8.5 wt %, and very preferably no greater than about 5 wt % of the solvent system;
[0035] · nitrile-containing compounds in an amount not greater than about 10%, preferably not greater than about 5% by weight of the solvent system;
[0036] A phosphorus-containing compound in an amount not greater than about 10% by weight of the solvent system; preferably not greater than about 5% by weight;
[0037] surfactant in an amount no greater than 20% by weight of the solvent system, preferably no greater than about 10% by weight of the solvent system, preferably no greater than about 8.5% by weight; and optionally
[0038] The total amount of the one or more additives does not exceed about 20% by weight of the solvent system, and desirably does not exceed about 16.5% by weight of the solvent system.
[0039] Optionally, the total amount of one or more additives does not exceed about 30% by weight of the solvent system.
[0040] In one aspect, the present invention provides a non-aqueous electrolyte composition comprising: one or more sodium-containing salts; and a solvent system comprising: a first component comprising one or more glyme-based solvents; and a second component as defined herein.
[0041] The second component may comprise or consist essentially of one or more additives selected from sulfur-containing compounds, boron-containing compounds, nitrile-containing compounds, phosphorus-containing compounds and surfactants.
[0042] Preferably, the second compound may comprise or consist essentially of one or more additives selected from sulfur-containing compounds in an amount of >0 wt % to ≤ 10 wt % of the solvent system.
[0043] The sulfur-containing compound may be present in an amount of >0.1 wt % to ≤10 wt % of the solvent system, preferably ≥0.2 wt % to ≤9 wt % of the solvent system, further preferably ≥0.3 wt % to ≤5 wt %, very preferably ≥0.4 wt % to ≤4 wt %, more preferably 0.5 wt % to ≤2.5 wt %, ideally 0.5 wt % to ≤2 wt %.
[0044] More preferably, the second component may comprise or consist essentially of one or more additives selected from boron-containing compounds in an amount of >0 wt % to ≤ 20 wt % of the solvent system.
[0045] The boron-containing compound may be present in an amount of >0 wt % to ≤ 15 wt % of the solvent system, preferably >0.4 wt % to ≤ 9 wt % of the solvent system, more preferably >1 wt % to ≤ 8.5 wt % of the solvent system.
[0046] Alternatively, the second component may comprise or consist essentially of one or more additives selected from nitrile-containing compounds in an amount of >0 wt % to ≤ 20 wt % of the solvent system.
[0047] The nitrile-containing compound may be present in an amount of >0.1 wt % to ≤15 wt % of the solvent system, preferably ≥0.2 wt % to ≤9 wt % of the solvent system, further preferably ≥0.3 wt % to ≤5 wt %, very preferably ≥0.4 wt % to ≤4 wt %, ideally 0.5 wt % to ≤3 wt %.
[0048] Alternatively, the second component may comprise or consist essentially of one or more additives selected from phosphorus-containing compounds in an amount of >0 wt % to ≤ 20 wt % of the solvent system.
[0049] The phosphorus-containing compound may be present in an amount of >0.1 wt % to ≤15 wt % of the solvent system, preferably ≥0.2 wt % to ≤9 wt % of the solvent system, further preferably ≥0.3 wt % to ≤5 wt %, very preferably ≥0.4 wt % to ≤4 wt %, ideally 0.5 wt % to ≤4 wt %.
[0050] Alternatively, the second component may comprise or consist essentially of one or more additives selected from surfactants in an amount of >0 wt % to ≤ 20 wt % of the solvent system.
[0051] The surfactant may be present in an amount of >0.1 wt% to ≤15 wt% of the solvent system, preferably ≥0.1 wt% to ≤9 wt% of the solvent system, more preferably ≥0.5 wt% to ≤7.5 wt% of the solvent system.
[0052] The second component may comprise or consist essentially of two or more additives.
[0053] Preferably, the second component may comprise or consist essentially of two or more additives comprising: a boron-containing compound and a surfactant. That is, one or more boron-containing compounds may be mixed with one or more surfactants to provide a mixture of two or more additives as the second component of the solvent system.
[0054] The second component may include two or more additives, the two or more additives including a boron-containing compound in an amount of >0 wt % to <20 wt % of the solvent system and a surfactant in an amount of >0 wt % to <20 wt % of the solvent system. In this embodiment, the total amount of the two or more additives is preferably no more than about 20 wt % based on the weight of the solvent system.
[0055] The second component may include two or more additives including a boron-containing compound in an amount of ≥ 0.5 wt % to < 20 wt % of the solvent system and a surfactant in an amount of ≥ 0.5 wt % to < 15 wt % of the solvent system.
[0056] Optionally, the total amount of two or more additives does not exceed about 20 weight percent based on the weight of the solvent system.
[0057] The second component may include two or more additives including a boron-containing compound in an amount of ≥ 0.5 wt % to < 10 wt % of the solvent system and a surfactant in an amount of ≥ 0.5 wt % to < 10 wt % of the solvent system.
[0058] Optionally, the total amount of two or more additives does not exceed about 10 wt % based on the weight of the solvent system.
[0059] The second component may include two or more additives including a boron-containing compound in an amount of ≥0.5 wt % to <5 wt % of the solvent system and a surfactant in an amount of >0.5 wt % to <5 wt % of the solvent system.
[0060] Optionally, the total amount of two or more additives does not exceed about 5 weight percent based on the weight of the solvent system.
[0061] The second component may include two or more additives, the two or more additives including a boron-containing compound in an amount of about 2% by weight of the solvent system and a surfactant in an amount of about 1% by weight of the solvent system. Optionally, in this embodiment, the total amount of the two or more additives does not exceed about 3% by weight based on the weight of the solvent system.
[0062] Alternatively, the second component may comprise or be substantially composed of two or more additives, the two or more additives comprising: a sulfur-containing compound and a surfactant. That is, one or more sulfur-containing compounds may be mixed with one or more surfactants to provide a mixture of two or more additives as the second component of the solvent system.
[0063] Further alternatively, the second component may comprise or consist essentially of two or more additives, the two or more additives comprising: a sulfur-containing additive and a boron-containing additive. That is, one or more sulfur-containing compounds may be mixed with one or more boron-containing compounds to provide a mixture of two or more additives as the second component of the solvent system.
[0064] The second component may comprise or consist essentially of three or more additives.
[0065] Preferably, the second component may comprise or consist essentially of three or more additives comprising:
[0066] Sulfur compounds;
[0067] Boron-containing compounds; and
[0068] Surfactant.
[0069] That is, one or more sulfur-containing compounds may be mixed with one or more boron-containing compounds and one or more surfactants to provide a mixture of three or more additives.
[0070] The second component may include three or more additives, the three or more additives comprising:
[0071] Sulfur-containing compounds in an amount of >0 wt % to <10 wt % of the solvent system,
[0072] a boron-containing compound in an amount of >0 wt% to <20 wt% of the solvent system, and
[0073] Surfactant in an amount of >0 wt% to <20 wt% of the solvent system.
[0074] The second component may include three or more additives, the three or more additives comprising:
[0075] Sulfur-containing compounds in an amount of >0 wt % to <10 wt % of the solvent system,
[0076] a boron-containing compound in an amount of >0 wt% to <10 wt% of the solvent system, and
[0077] Surfactant in an amount of >0 wt% to <10 wt% of the solvent system.
[0078] The second component may include three or more additives, the three or more additives comprising:
[0079] Sulfur-containing compounds in an amount of ≥0.5 wt % to <10 wt % of the solvent system,
[0080] a boron-containing compound in an amount of ≥ 0.5 wt % to < 10 wt % of the solvent system, and
[0081] Surfactant in an amount of ≥ 0.5 wt % to < 10 wt % of the solvent system.
[0082] Optionally, the total amount of the three or more additives does not exceed about 20 weight percent based on the weight of the solvent system.
[0083] The second component may include three or more additives, the three or more additives comprising:
[0084] Sulfur-containing compounds in an amount of >0 wt% to <5 wt% of the solvent system,
[0085] a boron-containing compound in an amount of >0 wt% to <5 wt% of the solvent system, and
[0086] Surfactant in an amount of >0 wt% to <5 wt% of the solvent system.
[0087] Alternatively, the second component may comprise three or more additives comprising:
[0088] Sulfur-containing compounds in an amount of ≥0.5 wt % to <5 wt % of the solvent system,
[0089] a boron-containing compound in an amount of ≥ 0.5 wt % to < 5 wt % of the solvent system, and
[0090] Surfactant in an amount of >0 wt% to <5 wt% of the solvent system.
[0091] Preferably, the total amount of the three or more additives does not exceed about 10 weight percent based on the weight of the solvent system.
[0092] More preferably, the total amount of the three or more additives does not exceed about 5 weight percent based on the weight of the solvent system.
[0093] The second component may include three or more additives, the three or more additives comprising:
[0094] Sulfur-containing compounds in an amount of about 2% by weight of the solvent system,
[0095] a boron-containing compound in an amount of about 1% by weight of the solvent system, and
[0096] Surfactant, in an amount of about 1 wt % of the solvent system.
[0097] The total amount of the three or more additives may be about 4 wt %, based on the weight of the solvent system.
[0098] The second component may include three or more additives, the three or more additives comprising:
[0099] Sulfur-containing compounds in an amount of about 0.5% by weight of the solvent system,
[0100] a boron-containing compound in an amount of about 2% by weight of the solvent system, and
[0101] Surfactant, in an amount of about 1 wt % of the solvent system.
[0102] The total amount of the three or more additives may be about 3.5 wt % based on the weight of the solvent system.
[0103] The second component may include three or more additives, the three or more additives comprising:
[0104] Sulfur-containing compounds in an amount of >0 wt % to ≤ 2.5 wt % of the solvent system,
[0105] a boron-containing compound in an amount of >0 wt% to ≤15 wt% of the solvent system, and
[0106] Surfactant in an amount of >0 wt % to ≤ 2.5 wt % of the solvent system.
[0107] Optionally, the total amount of the three or more additives does not exceed about 20 weight percent based on the weight of the solvent system.
[0108] The second component may include three or more additives, the three or more additives comprising:
[0109] Sulfur-containing compounds in an amount of >0 wt % to ≤ 2.5 wt % of the solvent system,
[0110] a boron-containing compound in an amount of >0 wt% to ≤2.5 wt% of the solvent system, and
[0111] Surfactant in an amount of >0 wt % to ≤ 15 wt % of the solvent system.
[0112] Optionally, the total amount of the three or more additives does not exceed about 20 weight percent based on the weight of the solvent system.
[0113] Alternatively, the second component may comprise or consist essentially of three or more additives comprising:
[0114] Nitrile-containing compounds;
[0115] Boron-containing compounds; and
[0116] Surfactant.
[0117] That is, one or more nitrile-containing compounds may be mixed with one or more boron-containing compounds and one or more surfactants to provide a mixture of three or more additives.
[0118] The second component may include three or more additives, the three or more additives comprising:
[0119] Nitrile-containing compounds in an amount of >0 wt % to <5 wt % of the solvent system,
[0120] a boron-containing compound in an amount of >0 wt% to <5 wt% of the solvent system, and
[0121] Surfactant in an amount of >0 wt% to <5 wt% of the solvent system.
[0122] Optionally, the total amount of the three or more additives does not exceed about 5 weight percent based on the weight of the solvent system.
[0123] The second component may comprise or consist essentially of four or more additives comprising:
[0124] Sulfur compounds;
[0125] Nitrile-containing compounds;
[0126] Boron-containing compounds; and
[0127] Surfactant.
[0128] That is, one or more sulfur-containing compounds may be mixed with one or more nitrile-containing compounds, one or more boron-containing compounds, and one or more surfactants to provide a mixture of four or more additives.
[0129] The second component may include four or more additives, the four or more additives comprising:
[0130] Sulfur-containing compounds in an amount of >0 wt% to <5 wt% of the solvent system,
[0131] Nitrile-containing compounds in an amount of >0 wt % to <5 wt % of the solvent system,
[0132] a boron-containing compound in an amount of >0 wt% to <5 wt% of the solvent system, and
[0133] Surfactant in an amount of >0 wt% to <5 wt% of the solvent system.
[0134] Optionally, the total amount of the four or more additives does not exceed about 20 weight percent based on the weight of the solvent system.
[0135] Optionally, the total amount of the four or more additives does not exceed about 10 wt % based on the weight of the solvent system.
[0136] Optionally, the total amount of the four or more additives does not exceed about 5 weight percent based on the weight of the solvent system.
[0137] In another aspect, the present invention provides a non-aqueous electrolyte composition consisting essentially of: one or more sodium-containing salts; and a solvent system consisting essentially of: a first component consisting essentially of one or more glyme-based solvents; and a second component as defined herein.
[0138] The one or more sodium-containing salts of the present invention may be defined as described herein.
[0139] The one or more sodium-containing salts (a) preferably comprise one or more weakly coordinating anions. The term "weakly coordinating anion" or "WCA" is well known to those skilled in the art and is used to refer to anions comprising several (more than one) elements, which may include halogen atoms and / or oxygen atoms, and which share a single negative charge. This means that the negative charge is spread over the anion and makes the coordination ability of the anion relatively weak, for example, weaker relative to anions with concentrated negative charges or anions with multiple negative charges.
[0140] Preferably, the sodium-containing salt is selected from one or more of the formula NaM m X x one or more compounds of the formula NaXO4; one or more sodium salts of fluorinated sulfonyl compounds; one or more sodium salts of fluorinated sulfonate compounds; one or more sodium salts of oxalato borate compounds; one or more sodium salts of difluorooxalato borate compounds; and one or more tetrahedral anions such as tetrakis[3,5-bis(trifluoromethyl)phenylborate anion (B[3,5-(CF3)2C6H3] - 4. Tris(pentafluorophenyl)borate anion (B(C6F5) - 4) and tetracarboxy(trifluoromethyl)aluminate anion (Al[OC(CF3)3] - 4).
[0141] Very preferably, the one or more sodium-containing salts are selected from: one or more of the formula NaM m X x wherein M is one or more metals and / or non-metals, and X is a group comprising or consisting of one or more halogens; sodium salts of one or more fluorinated sulfonyl compounds; sodium salts of one or more fluorinated sulfonate compounds; sodium salts of one or more oxalato borate compounds; and sodium salts of one or more difluorooxalato borate compounds.
[0142] In one or more preferred formulas NaM m X x In the sodium-containing salt, M is one or more metals and / or non-metals and X is a group containing or consisting of one or more halogens, which are preferably selected from fluorine, chlorine, bromine and iodine, and more preferably fluorine. The amount x of the halogen X is preferably x=1 to 16, and more preferably x=4 or 6. The amount m of the one or more metals and / or non-metals M is preferably m=1 to 3, and more preferably m=1 to 2, and particularly preferably m=1. Ideally, the one or more metals and / or non-metals M are preferably selected from aluminum, boron, gallium, indium, iridium, platinum, scandium, yttrium, lanthanum, antimony, arsenic and phosphorus. Particularly preferably, M is selected from aluminum, boron, gallium, phosphorus and arsenic. The most preferred general formula NaM n X x The sodium salt is selected from one or more of sodium tetrafluoroborate (NaBF4) and sodium hexafluorophosphate (NaPF6).
[0143] In the preferred sodium compound of the formula NaXO4, the element X is preferably one or more halogens selected from fluorine, chlorine, bromine and iodine. Chlorine is particularly preferred, and the most preferred sodium salt of the formula NaXO4 is NaClO4. Preferred sodium salts of the fluorine-containing sulfonyl compound(s) include sodium bis(fluorosulfonyl)imide (also known as NaFSI(NaN(SO2F)2)) and sodium bis(trifluoromethanesulfonyl)imide (also known as NaTFSI(C2F6NNaO4S2)). Preferred sodium salts of the fluorine-containing sulfonate compound(s) include sodium trifluoromethanesulfonate, also known as sodium trifluoromethanesulfonate or NaOTf(CF3NaSO3). Preferred sodium salts of the oxalate borate compound(s) include sodium bis(oxalate), also known as borate NaBOB or NaB(C2O4)2; and sodium difluoro(oxalato)borate, also known as NaDFOB.
[0144] Very preferably, the one or more sodium-containing salts are selected from sodium tetrafluoroborate (NaBF4), sodium hexafluorophosphate (NaPF6), sodium trifluoromethanesulfonate (CF3NaSO3), sodium bis(fluorosulfonyl)imide (Na(SO2F)2N), sodium bis(trifluoromethanesulfonyl)imide (C2F6NNaO4S2), bis(sodium oxalate) (NaB(C2O4)2) and sodium difluoro(oxalato)borate. Most preferably, the one or more sodium-containing salts are sodium tetrafluoroborate (NaBF4).
[0145] The amount of the one or more sodium-containing salts is conveniently expressed as a molar concentration of the components in the solvent system; that is, the total number of moles of the one or more sodium-containing salts (i.e., solute) per kilogram of the solvent system (the combined weight of the first component and the second component), i.e., mol / kg.
[0146] Preferably, each sodium-containing salt has a molar concentration in the range of 0.1 mol / kg to 5 mol / kg, and further preferably in the range of 0.1 mol / kg to ≤2.5 mol / kg. Very preferably, especially when the component is NaBF4, the molar concentration is in the range of 0.1 mol / kg to ≤2.5 mol / kg, most preferably about 1.5 mol / kg. The total molar concentration of all sodium-containing salts is preferably in the range of 0.1 mol / kg to 10 mol / kg, more preferably in the range of 0.1 mol / kg to 6 mol / kg, and most preferably in the range of 0.1 mol / kg to ≤4 mol / kg.
[0147] The one or more glyme-based solvents of the present invention may be defined as described herein.
[0148] The one or more glycol dimethyl ether-based solvents present in the first solvent component can be saturated non-cyclic polyethers preferably free of other functional groups. Glyme is also known as glycol diether. Suitable glycol dimethyl ether-based solvents can be selected from: ethylene glycol dimethyl ether (monoglycole dimethyl ether CH3-O-CH2CH2-O-CH3); diethylene glycol dimethyl ether (diglyme dimethyl ether CH3-O-(CH2-CH2-O)2-CH3); triethylene glycol dimethyl ether (triglyme dimethyl ether, CH3-O-(CH2CH2-O)3-CH3); tetraethylene glycol dimethyl ether (tetraglycole dimethyl ether, CH3-O-(CH2CH2-O)4-CH3); ethylene glycol diethyl ether (glycole diethyl ether, CH3CH2-O-CH2CH2 -O-CH2CH3); diethylene glycol diethyl ether (diethylene glycol diethyl ether, CH3CH2-O-(CH2CH2-O)2-CH2CH3); ethylene glycol dibutyl ether (ethylene glycol dibutyl ether, CH3CH2CH2CH2-O-CH2CH2-O-CH2CH2CH2CH3); diethylene glycol dibutyl ether (diethylene glycol dibutyl ether, CH3CH2CH2CH2-O-(CH2CH2-O)2-CH2CH2CH2CH3); polyethylene glycol dimethyl ether (polyethylene glycol dimethyl ether, CH3-O-(CH2CH2-O) n -CH3); and dipropylene glycol dimethyl ether (dipropylene glycol dimethyl ether (proglyme), CH3-O-(CH2CH2CH2-O)2-CH3).
[0149] Very suitable glyme-based solvents can be selected from ethylene glycol dimethyl ether (monoglyme), diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme) and tetraethylene glycol dimethyl ether (tetraglyme). Diethylene glycol dimethyl ether (diglyme) and tetraethylene glycol dimethyl ether (tetraglyme) are particularly preferred glyme-based solvents.
[0150] Preferred nonaqueous electrolyte compositions of the present invention comprise a solvent system comprising a first component consisting essentially of diglyme and / or tetraglyme.
[0151] Alternatively, the nonaqueous electrolyte composition of the present invention comprises a solvent system comprising a first component consisting essentially of a combination of diglyme and / or tetraglyme and one or more additional glyme-based compounds.
[0152] When a mixture of glyme-based compounds is used, it is convenient to express the amount of each of the one or more glyme-based solvents in terms of a weight ratio. For example, as discussed above, a highly preferred glyme-based solvent comprises a mixture of diglyme and tetraglyme, and this will ideally be in a weight ratio of 1 to 20: 1 to 20 weight / weight, further preferably in a weight ratio of 1 to 10: 1 to 10 weight / weight, also preferably in a weight ratio of 1 to 5: 1 to 5 weight / weight, and most preferably in a weight ratio of 1: 1 weight / weight.
[0153] Highly advantageous electrolyte compositions of the present invention comprise one or more glyme-based solvents in an amount of at least about 40 wt %, preferably at least about 50 wt %, and more preferably at least about 60 wt % of the glyme-based solvent (i.e., the first component of the solvent system).
[0154] For the avoidance of any doubt, the phrase "the weight of the solvent system" as used herein refers to the sum of the weight of the first component of the solvent system and the weight of the second component of the solvent system.
[0155] Very preferably, diglyme and tetraglyme are used as the glyme-based solvent in a 50% by weight combination. That is to say:
[0156] diglyme is present in an amount of about 50% by weight of the first component of the solvent system; and
[0157] Tetraglyme is present in an amount of about 50% by weight of the first component of the solvent system.
[0158] Thus, the total amount of diglyme and tetraglyme is preferably about 100% by weight of the first component of the solvent system.
[0159] As discussed above, the non-aqueous electrolyte composition according to the present invention may include one or more surfactants. The one or more surfactants of the present invention may be defined as described herein.
[0160] Based on the total weight of the electrolyte solvent system used in the electrolyte composition, the total amount of one or more surfactants used in the electrolyte composition of the present invention can be >0.2 wt% to ≤20 wt% of the solvent system, preferably ≥0.2 wt% to ≤10 wt% of the solvent system, further preferably ≥0.2 wt% to ≤4 wt%, very preferably ≥0.5 wt% to ≤3 wt%, ideally 0.5 wt% to ≤2.5 wt%.
[0161] The amount of one or more surfactants used in the second component of the electrolyte composition of the present invention can be >0 wt % of the solvent system, desirably >0.2 wt %, preferably >0.5 wt % of the solvent system, based on the total weight of the electrolyte solvent system used in the electrolyte composition.
[0162] In a preferred embodiment, one or more surfactant additives used in the second component of the present invention are preferably selected to enhance the ability of the electrolyte composition to wet the separator (particularly polyolefin separator) and / or electrode of the battery, which in turn advantageously promotes a longer battery cycle life. In addition, it is known in the literature that surfactants can cause non-dendritic metal plating / stripping (and also inhibit corrosion) due to their surface adsorption on different substrates. Preferred one or more surfactant additives are selected from anionic surfactants, cationic surfactants, nonionic (hydrophilic) surfactants and amphoteric (zwitterionic) surfactants, with anionic surfactants and nonionic (hydrophilic) surfactants being particularly preferred. Such surfactant additives are ideally selected from one or more of the following:
[0163] 1) Anionic (negatively charged) surfactants. Suitable examples include: carboxylates (such as alkyl carboxylates (e.g., fatty acid salts)), carboxylate fluorosurfactants; sulfates (such as alkyl sulfates (e.g., sodium lauryl sulfate), alkyl ether sulfates (e.g., sodium lauryl ether sulfate)); sulfonates (such as docusates (e.g., sodium dioctyl sulfosuccinate) and alkylbenzene sulfonates); and phosphates (such as alkyl aryl ether phosphates and alkyl ether phosphates (e.g., trioctyl phosphate);
[0164] 2) Zwitterionic (amphoteric) surfactants, which can be anionic, cationic or nonionic, depending on the pH of the solution in which they are located. Examples include: RN + H2CH2COO - , RN + (CH3)2CH2CH2SO3 - , phospholipids (such as phosphatidylcholine (lecithin));
[0165] 3) Cationic surfactants with positive charge, such as RN + H3Cl- , RN + (CH3)3Cl - , diotadecyldimethylammonium chloride, cetylpyridinium chloride, benzalkonium chloride, cetyltrimethylammonium chloride (CTAC), and cetyltrimethylammonium bromide (CTAB); and
[0166] 4) Nonionic surfactants. These are uncharged and examples include: polyol esters (e.g. glycols, glycerides, sorbitan and sorbitan derivatives such as fatty acid esters of sorbitan (Spans, ) and their ethoxylated derivatives (Tweens, )), polyoxyethylene esters and poloxamers containing block copolymers, such as poloxamer 84, poloxamer 105, poloxamer 123, poloxamer 124, poloxamer 188, poloxamer 237, poloxamer 338, poloxamer 407 and poloxamer F127.
[0167] Most preferably, the surfactant of the non-aqueous electrolyte composition of the present invention comprises one or more surfactants containing nonionic block copolymers, and / or surfactants containing anionic phosphates. Very suitable examples include poloxamers and / or alkyl ether phosphates (e.g., trioctyl phosphate) as described above.
[0168] As discussed above, the non-aqueous electrolyte composition according to the present invention may include one or more sulfur-containing compounds. The one or more sulfur-containing compounds of the present invention may be defined as described herein.
[0169] The sulfur-containing compound used in the second solvent component of the present invention is preferably selected so as to enable the formation of a stable cathode-electrolyte interface (CEI) at the cathode and / or a stable solid-electrolyte interface (SEI) at the anode, which in turn leads to advantages such as enhanced first cycle coulombic efficiency (FCE=first cycle coulombic efficiency) and enhanced cycle life; alternatively, such additives may significantly decompose preferentially in the first cycle, which may result in low first cycle efficiency, but then improve subsequent cycle stability.
[0170] Suitable sulfur-containing compounds may include cyclic and / or acyclic sulfur-containing compounds.
[0171] Preferably, the sulfur-containing compound is a sulfone, a sulfate or a sulfonate.
[0172] In other words, the sulfur-containing compound can have a sulfonyl functional group attached to two carbon atoms (sulfone), two oxygen atoms (sulfate), or one carbon atom and one oxygen atom (sulfonate) in a cyclic or non-cyclic structure. When the sulfonate is cyclic, the compound can be referred to as a sultone.
[0173] As used herein, the term "sulfone" means a central hexavalent sulfur atom double-bonded to each of two oxygen atoms and having a single bond to each of two carbon atoms.
[0174] As used herein, the term "sulfate" means a central hexavalent sulfur atom double-bonded to two of the oxygen atoms and having single bonds to two additional oxygen atoms, each of which is further single-bonded to a carbon atom.
[0175] As used herein, the term "sulfonate" means a central hexavalent sulfur atom double-bonded to two oxygen atoms; which has a single bond to one carbon atom; and a single bond to another oxygen atom, which is further single-bonded to a carbon atom, which, if cyclically linked to another carbon atom bonded to the sulfur atom, would be a sultone.
[0176] The general formula of this compound is RY(S=O)2Y'R', wherein:
[0177] Y and Y' are independently selected from C or O (ie they may be the same or different from each other);
[0178] when Y and Y' are identical, R and R' may be independently selected from (i.e. they may be identical to or different from each other) any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or wherein R and R' may independently or together form a substituted or unsubstituted C3-C6-cycloalkyl, phenyl or heterocyclic containing group; and
[0179] When Y and Y' are different from each other, R' can be independently selected from any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or wherein R and R' can independently or together form a substituted or unsubstituted C3-C6-cycloalkyl, cycloalkenyl, phenyl or heterocyclic group.
[0180] In some embodiments, the general formula of such compounds is R-SO2-R', wherein R and R' can be independently selected from (i.e., they can be the same or different from each other) any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or wherein R and R' can independently or together form a substituted or unsubstituted C3-C6-cycloalkyl, phenyl or heterocyclic group.
[0181] Preferably, such compounds have the general formula RO(S=O)2OR', wherein R and R' can be independently selected from (i.e. they can be the same or different from each other) any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or wherein R and R' can independently or together form a substituted or unsubstituted C3-C6-cycloalkyl, phenyl or heterocyclic group.
[0182] Very preferably, the sulfur-containing compound is selected from cyclic sulfates (such as 1,3-propylene glycol cyclic sulfate (PCS), also known as 1,3,2-dioxathiolane 2,2-dioxide (DTD or (CH2)3SO4)); 1,5,2,4-dioxadithiolane 2,2,4,4-tetraoxide; or 1,3,2-dioxathiolane 2,2-dioxide. 1,3-propylene glycol cyclic sulfate (PCS) is particularly preferred. Suitable examples of cyclic sulfones include: sulfolane ((CH2)4SO2), 3-methylsulfolane ((CH3)CH(CH2)3SO2) and trimethyl sulfone ((CH2)3SO2). Suitable examples of non-cyclic sulfones include: methyl phenyl sulfone ((CH3)(C6H5)SO2).
[0183] Suitable examples among the examples of sultone include: 1-propylene 1,3-sultone ((CH)2CH2SO3) and 1,3-propane sultone (CH2)3SO3).
[0184] Based on the total weight of the electrolyte solvent system used in the electrolyte composition, the total amount of one or more sulfur-containing compounds used in the electrolyte composition of the present invention can be >0.5 wt% to ≤10 wt% of the solvent system, preferably ≥0.6 wt% to ≤6 wt% of the solvent system, further preferably ≥0.6 wt% to ≤4 wt%, very preferably ≥0.6 wt% to ≤3 wt%, ideally 0.6 wt% to ≤2.5 wt%.
[0185] The amount of one or more sulfur-containing compounds used in the second component of the electrolyte composition of the present invention can be >0 wt % of the solvent system, desirably >0.2 wt %, preferably >0.5 wt % of the solvent system, based on the total weight of the electrolyte solvent system used in the electrolyte composition.
[0186] As discussed above, the non-aqueous electrolyte composition according to the present invention may comprise one or more boron-containing compounds. The one or more boron-containing compounds of the present invention may be defined as described herein.
[0187] The boron-containing compound used in the second solvent component of the present invention is preferably selected to enable the formation of a stable cathode-electrolyte interface (CEI) at the cathode and / or a stable solid-electrolyte interface (SEI) at the anode, which in turn leads to advantages such as enhanced first cycle Coulombic efficiency and / or enhanced cycle life.
[0188] Suitable boron-containing compounds may include cyclic and / or acyclic boron-containing compounds.
[0189] Preferably, the one or more boron-containing compounds are borate esters or boroxines.
[0190] In other words, one or more boron-containing compounds may have a central boron atom connected to three oxygen atoms, each of which is further single-bonded to a carbon or silicon atom (boric acid ester). Or one or more boron-containing compounds may comprise a 6-membered heterocyclic structure consisting of three alternating boron atoms and oxygen atoms connected together by a shared single bond. Each boron atom is further individually bonded to a carbon atom or oxygen outside the heterocyclic structure.
[0191] As used herein, the term "borate ester" refers to a central trivalent boron atom singly bonded to three oxygen atoms, each of which is further singly bonded to a carbon or silicon atom.
[0192] As used herein, the term "boroxine" refers to a 6-membered heterocyclic compound composed of alternating single-bonded trivalent boron atoms and divalent oxygen atoms, each boron atom further single-bonded to an oxygen or carbon atom outside the heterocyclic structure.
[0193] The general formula of such borate ester compounds is B(OYR)3, where Y and R can be the same or different in each individual attachment instance. More specifically, this can be written as:
[0194] B(OYR)(OY'R')(OY”R”), where
[0195] Y, Y' and Y" are independently selected from C or Si (ie they may be the same or different from each other); and
[0196] R, R' and R" may be independently selected from hydrogen; any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or a substituted or unsubstituted C3-C6-cycloalkyl, phenyl or heterocyclic group.
[0197] More preferably, the boron-containing compound is selected from acyclic borate esters.
[0198] Suitable examples include tris(trimethylsilyl)borate (TMSB);
[0199] Tris(2,2,2-trifluoroethyl)borate;
[0200] trimethyl borate; and
[0201] Triethyl borate
[0202] Tris(trimethylsilyl)borate (TMSB) is a particularly preferred example.
[0203] The general formula of such boroxine compounds is B3(YR)3O3, where Y and R can be the same or different in each individual instance of attachment. More specifically, this can be written as:
[0204] B a (YR) b (O) c ,in
[0205] Y is independently selected from C or O (ie they may be the same or different from each other); and
[0206] R may be identical or different in each individual case and may be independently selected from hydrogen; any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or a substituted or unsubstituted C3-C6-cycloalkyl-, phenyl- or heterocyclic-containing group; and
[0207] a=b=c, where a, b and c are each 3.
[0208] Suitable examples include:
[0209] trimethoxyboroxine; and
[0210] Trimethylboroxine.
[0211] The amount of one or more boron-containing compounds used in the second component of the electrolyte composition of the present invention can be >0 wt % of the solvent system, desirably >0.2 wt %, preferably >0.5 wt % of the solvent system, based on the total weight of the electrolyte solvent system used in the electrolyte composition.
[0212] As discussed above, the non-aqueous electrolyte composition according to the present invention may include one or more nitrile-containing compounds. The one or more nitrile-containing compounds of the present invention may be defined as described herein.
[0213] The nitrile-containing compound used in the second solvent component of the present invention is preferably selected to enable the formation of a stable cathode-electrolyte interface (CEI) at the cathode and / or a stable solid-electrolyte interface (SEI) at the anode, which in turn leads to advantages such as enhanced first cycle Coulombic efficiency and / or enhanced cycle life.
[0214] Suitable examples include: adiponitrile, glutaronitrile, acetonitrile and 1,3-6-hexanetonitrile. 1,3-6-hexanetonitrile is a particularly preferred example.
[0215] The amount of one or more nitrile-containing compounds used in the second component of the electrolyte composition of the present invention can be >0 wt % of the solvent system, desirably >0.2 wt %, preferably >0.5 wt % of the solvent system, based on the total weight of the electrolyte solvent system used in the electrolyte composition.
[0216] As discussed above, the non-aqueous electrolyte composition according to the present invention may include one or more phosphorus-containing compounds. The one or more phosphorus-containing compounds of the present invention may be defined as described herein.
[0217] The phosphorus-containing compound used in the second solvent component of the present invention is preferably selected to enable the formation of a stable cathode-electrolyte interface (CEI) at the cathode and / or a stable solid-electrolyte interface (SEI) at the anode, which in turn leads to advantages such as enhanced first cycle Coulombic efficiency and / or enhanced cycle life.
[0218] Preferably, the phosphorus-containing compound is a phosphite- or phosphate-containing compound.
[0219] Suitable examples include tris(trimethylsilyl)phosphite (TMSP) or tris(trimethylsilyl)phosphate.
[0220] The amount of one or more phosphorus-containing compounds used in the second component of the electrolyte composition of the present invention can be >0 wt % of the solvent system, desirably >0.2 wt %, preferably >0.5 wt % of the solvent system, based on the total weight of the electrolyte solvent system used in the electrolyte composition.
[0221] The nonaqueous electrolyte composition according to the present invention may further comprise one or more additional compounds which may or may not be a solvent.
[0222] Examples of such additional compounds include flame retardant compounds (such as compounds containing polyalkyl phosphates, preferably compounds containing non-fluorinated polyalkyl phosphates), diluents (such as compounds containing hydrofluoroethers, preferably compounds containing hydrofluoroalkyl ethers), glycol ether acetates, ionic liquids, and any solvents that can promote the reduction of electrolyte viscosity by acting as an inert diluent (such as hydrofluoroalkyl ethers, preferably 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (HFE or TTE)).
[0223] The electrolyte composition according to the present invention may also optionally contain one or more performance additives, the amount of which is generally <15 wt %, preferably <10 wt %, and further preferably 0.1 wt % to <5 wt % of the total weight of the solvent system used in the electrolyte composition. Such performance additives preferably act at the electrolyte-electrode interface rather than in the bulk of the electrolyte.
[0224] Suitable performance additives may be selected from: polymerizable additives for promoting overcharge protection, such as biphenyl, diphenylamine, dimethoxydiphenylsilane (DDS), 3-chloroanisole (3CA), N-phenylmaleimide, xylene (methyl substituted benzene) and cyclohexylbenzene; additives based on redox shuttle mechanisms for promoting overcharge protection, such as 2,5-di-tert-butyl-1,4-dimethoxybenzene (DDB), 4-tert-butyl-1,2-dimethoxybenzene (TDB), 1,4-bis(trimethylsilyl)-2,5-dimethoxybenzene (BTMSDB) and 1,4-bis(2-methoxyethoxy) additives for imparting further flame retardant properties to the electrolyte, such as dimethyl methylphosphonate (DMMP), ethoxy-pentafluoro-cyclotriphosphazene (N3P3F5OCH2CH3, EFPN), tris(2,2,2-trifluoroethyl)phosphite and / or tris(2,2,2-trifluoroethyl)phosphate (TFEP), methyl nonafluorobutyl ether (MFE) and silane-Al2O3 nanoparticles; additives for promoting better high temperature cycling, such as succinic anhydride; and additives for in situ generation of inert unwanted decomposition products (such as HF, water or CO2), such as zeolites.
[0225] The non-aqueous electrolyte composition of the present invention is particularly suitable for anode-free sodium batteries, also known as in-situ sodium plating batteries. Such anode-free sodium batteries can be used in energy storage devices such as batteries, rechargeable batteries, electrochemical devices and electrochromic devices.
[0226] Thus, in one aspect, the present invention provides an anode-free sodium battery comprising a non-aqueous electrolyte composition as defined herein. More specifically, in one aspect, the present invention provides:
[0227] An anode-free sodium battery comprising:
[0228] a cathode comprising a sodium-containing active material;
[0229] Anode current collector;
[0230] a separator positioned between the cathode and anode current collectors; and
[0231] A non-aqueous electrolyte composition as defined herein.
[0232] Another aspect of the present invention also provides use of the non-aqueous electrolyte composition defined herein in an anode-free sodium battery.
[0233] In another aspect, the present invention also provides a method of operating an anode-free sodium battery as defined herein.
[0234] Preferably, the anode-free sodium battery has a charge cutoff voltage of 4.0 V or higher.
[0235] In another aspect, the invention also provides a device comprising one or more anode-free sodium batteries as defined herein. For example, a general device may include equipment such as a battery pack, which may be used in stationary or mobile applications.
[0236] As used herein, "anode-free sodium battery" refers to a battery in which the operating principle of the battery involves the extraction / insertion of sodium metal cations (Na + ) and deposition and plating / removal and stripping of sodium metal (Na) at the anode current collector.
[0237] During the first charge cycle of the anode-free sodium battery, a sodium metal anode is formed in situ on the anode current collector as sodium metal cations are reduced and deposited as sodium metal on the anode current collector.
[0238] When the anode-less sodium battery is fully discharged, the anode current collector contains only trace amounts of sodium metal or significantly less sodium metal than is the case for a fully charged battery, most of the sodium metal having been oxidized to form sodium metal cations that are present in the electrolyte and / or stored in the cathode.
[0239] When the anode-free sodium battery is fully charged, the anode current collector includes a sodium layer in electrical contact with the anode current collector, and the amount of sodium in the cathode is correspondingly less. The sodium layer in electrical contact with the anode current collector may span the entire surface of the anode current collector, or it may be deposited in some areas of the anode current collector. However, where sodium is deposited, it is preferred that any such sodium layer is uniform and homogenous.
[0240] The anode-free battery disclosed herein may include a separator between the cathode and anode current collectors. The electrolyte nonaqueous electrolyte composition according to the present invention has particular utility when used in an anode-free battery comprising a polyolefin separator.
[0241] The cathode generally comprises a sodium-containing active material disposed on one or more surfaces of a (cathode) current collector.
[0242] The cathode current collector and the anode current collector can each be independently made of any suitable conductive material. For example, the cathode current collector, the anode current collector, or both the cathode current collector and the anode current collector can be formed of a metal; the metal is such as nickel, aluminum, titanium, copper, gold, silver, platinum, aluminum alloy, stainless steel or any other metal substrate (similar to the current collectors commonly used in current sodium ion batteries.
[0243] The cathode current collector, the anode current collector, or both the cathode current collector and the anode current collector may be formed of aluminum or an aluminum alloy (e.g., an alloy of aluminum and one or more of Mg, Mn, Cr, Zn, Si, Fe, and Ni). Very preferably, both the cathode current collector and the anode current collector include an aluminum current collector. Alternatively, copper, magnesium, carbon paper / foil / substrate, and tin may also be used as current collector materials.
[0244] The cathode current collector and the anode current collector can be formed into any suitable shape compatible with the overall design of the electrochemical cell. For example, the cathode current collector and the anode current collector can each be independently formed into a foil, a flat plate, a mesh, a net, a lath, a perforated metal or an embossing, or a combination of these shapes (e.g., a mesh flat plate). If desired, irregularities can be formed on one or more surfaces of the cathode current collector and / or the anode current collector, for example by etching one or more surfaces of the current collector.
[0245] Most preferably, the anode current collector is formed of aluminum or an aluminum alloy, and comprises a foil or mesh shape.
[0246] Preferably, before the initial first charging cycle of the anode-free sodium battery, the anode current collector further comprises one or more nucleation layers formed on one or more surfaces of the anode current collector. Very preferably, such one or more nucleation layers comprise one or more carbon-containing nucleation layers.
[0247] Since the anode current collector has one or more nucleation layers formed on one or more surfaces of the anode current collector, metal cations are reduced and deposited as sodium metal on the one or more nucleation layers during the first charging cycle of the anode-free sodium battery.
[0248] As used herein, the term "nucleation layer" refers to any coating or layer disposed on one or more surfaces of a "virgin" anode current collector prior to the initial first charge cycle of an anode-free sodium battery. The use of a nucleation layer enables more uniform and homogeneous sodium metal deposition than a current collector without such a nucleation layer.
[0249] A particularly preferred nucleation layer is any coating or layer that will result in a reduction in the "nucleation overpotential" for sodium metal electroplating.
[0250] When sodium metal is deposited on the anode current collector via constant current (galvanostatic) cycling, for the same constant current value, during steady-state conditions, the potential rises to a higher value (but still below 0 V vs. Na / Na + ) before the sodium plating potential will first decrease (to below 0 V vs. Na / Na + more negative values).
[0251] Thus, the "nucleation overpotential" for sodium deposition is defined herein as the difference between the most negative potential and the steady-state plating potential. Thus, one skilled in the art can readily measure the nucleation overpotential for sodium deposition using an anode current collector comprising one or more nucleation layers formed on the surface of the anode current collector and compare it to the nucleation overpotential for sodium deposition using a "pristine" anode current collector to determine the preferred nucleation layer described herein. This can be done in a half-cell or three-electrode cell constructed using common knowledge.
[0252] As discussed above, advantageously, the one or more nucleation layers enable deposition of sodium metal atoms and radicals on and across the surface of the anode current collector, thereby facilitating more uniform electroplating while also minimizing parasitic reactions.
[0253] One or more nucleation layers may be formed across a majority (or the entire 100%) of one or more surfaces of the anode current collector, or may be formed by design as a partial coating (e.g., one or more nucleation layers are formed on some regions of such surface - these regions will be homogenous and uniform within the region).
[0254] The one or more nucleation layers preferably include one or more negative electrode active material layers (e.g., thin layers such as 0.1 μm to 1000 μm), which may or may not be mixed with any type of conductive additive, such as carbon black (to enhance the electronic conductivity of the negative electrode active material) and / or a binder material that is compatible with water or an organic solvent.
[0255] Most preferably, the one or more nucleation layers comprise one or more carbon-containing nucleation layers, and most preferably, the one or more carbon-containing nucleation layers have a thickness of about 10 Angstroms to about 1000 μm.
[0256] Suitable one or more carbon-containing nucleation layers may include: carbon black, carbon nanotubes, carbon nanofibers, graphite / graphene, hard carbon, glassy carbon, soft carbon, activated carbon (e.g., in fiber form), or combinations thereof. In some cases, the carbon-containing nucleation layer may include amorphous carbon (e.g., carbon black, such as Super C65). Techniques such as doctor blade coating, slot die coating, ultrasonic spray deposition, screen printing, physical vapor deposition (PVD) and chemical vapor deposition (CVD) can also be used to prepare the carbon-containing nucleation layer.
[0257] The one or more carbon-containing nucleation layers may further comprise one or more binders and / or conductive additives.
[0258] Examples of the one or more binders include polymers such as PAA, PVDF, PEO, PTFE, SBR (styrene butadiene rubber), acrylic emulsion polymers, cellulosic polymers (eg, CMC), copolymers thereof, and blends thereof.
[0259] In some embodiments, the nucleation layer (preferably a carbon-containing nucleation layer) may be less than 2 mg / cm 2 An area loading of less than 1.75 mg / cm2 is present on the surface of the anode current collector (based on the weight of the active material (e.g., C65) and excluding, for example, optional binders and / or additives, etc.) 2 Less than 1.5mg / cm 2 , less than 1.25mg / cm 2 Less than 1mg / cm 2 , less than 900μg / cm 2 , less than 800μg / cm 2 , less than 700μg / cm 2 , less than 600μg / cm 2 Less than 500 μg / cm 2 , less than 400μg / cm 2 Less than 300 μg / cm 2 Less than 200 μg / cm 2 Less than 100 μg / cm 2 or less than 50 μg / cm 2 ).
[0260] In some embodiments, the nucleation layer (preferably a carbon-containing nucleation layer) may be at least 20 μg / cm 2 An area loading of at least 50 μg / cm 2 , at least 100 μg / cm 2, at least 200 μg / cm 2 , at least 300 μg / cm 2 , at least 400 μg / cm 2 , at least 500 μg / cm 2 , at least 600 μg / cm 2 , at least 700 μg / cm 2 , at least 800 μg / cm 2 , at least 900 μg / cm 2 , at least 1mg / cm 2 , at least 1.25mg / cm 2 , at least 1.5 mg / cm 2 or at least 1.75 mg / cm 2 .
[0261] In some embodiments, the nucleation layer (preferably a carbon-containing nucleation layer) can be present on the surface of the first metal current collector at an area loading ranging from any of the minimum values described above to any of the maximum values described above. For example, the nucleation layer can be present at 20 μg / cm 2 Up to 2mg / cm 2 , 50μg / cm 2 Up to 2mg / cm 2 , 100μg / cm 2 Up to 2mg / cm 2 , 200μg / cm 2 Up to 2mg / cm 2 , 400μg / cm 2 Up to 2mg / cm 2 , 20μg / cm 2 Up to 1mg / cm 2 , 50μg / cm 2 Up to 1mg / cm 2 , 100μg / cm 2 Up to 1mg / cm 2 , 200μg / cm 2 Up to 1mg / cm 2 or 400 μg / cm 2 Up to 1mg / cm 2 An area loading of is present on the surface of the first metal current collector.
[0262] Nucleation is a surface process. Therefore, the nucleation layer (preferably a carbon-containing nucleation layer) can be a monoatomic layer thickness in principle to provide an interface (surface) for sodium nucleation. In some embodiments described herein, the nucleation layer (preferably a carbon-containing nucleation layer) can have a thickness of 1000 angstroms or less (e.g., 500 angstroms or less, 100 angstroms or less, 50 angstroms or less, 30 angstroms or less, 25 angstroms or less, 20 angstroms or less, or 10 angstroms or less).
[0263] Alternatively, before the initial first charging cycle of the anode-free sodium battery, the anode current collector further comprises two or more nucleation layers formed on one or more surfaces of the anode current collector. In one embodiment, such two or more nucleation layers are preferably two or more carbon-containing nucleation layers.
[0264] Alternatively, before the initial first charge cycle of the anode-free sodium battery, the anode current collector disclosed herein does not include one or more nucleation layers on one or more surfaces of the anode current collector. Therefore, before the initial first charge cycle of the anode-free sodium battery, the anode current collector is "pristine".
[0265] As used herein, the phrase "pristine" refers to the state of the anode-free sodium battery in its "as manufactured" state prior to the initial first charge cycle. In other words, the anode current collector is substantially the pure material from which it is formed, free of impurities (e.g., surface oxide layer, etc.). As such, the anode current collector is not coated with one or more nucleation layers (as discussed above), conventional active materials, binders, etc.
[0266] After charge and discharge cycles, the anode current collector in a completely sodium-stripped state may be the same as the "pristine" state, or it may incorporate one or more layers substantially comprising sodium-containing materials. It may also contain inorganic-rich and / or organic-rich materials from, for example, the electrolyte composition and its decomposition products.
[0267] Based on the disclosure herein, it is believed that any type of sodium-containing active material may be used as the cathode to form an anode-free sodium battery according to the present invention.
[0268] Examples of these include sodium transition metal oxides, polyanionic compounds (including fluorinated polyanionic compounds), Prussian blue compounds (and their analogs such as Prussian white or Berlin green), materials that store sodium via conversion reactions, sodium transition metal fluorides, oxyfluorides, phosphates, sulfates and silicates (and their fluorinated forms). Preferred examples are sodium transition metal oxides.
[0269] Preferred sodium transition metal oxides have the general formula:
[0270] A 1±δ M 1 V M 2 W M 3 X M 4 Y M 5 Z O 2-c
[0271] in
[0272] A is one or more alkali metals selected from sodium, potassium and lithium;
[0273] M 1 comprising one or more redox-active metals in oxidation state +2, preferably selected from nickel, copper, cobalt and manganese;
[0274] M 2 comprising a metal in an oxidation state greater than 0 to less than or equal to +4;
[0275] M 3 Contains a metal in oxidation state +2;
[0276] M 4 comprising a metal in an oxidation state greater than 0 to less than or equal to +4;
[0277] M 5 Contains a metal in oxidation state +3;
[0278] in
[0279] 0≤δ≤1;
[0280] V>0;
[0281] W ≥ 0;
[0282] X ≥ 0;
[0283] Y ≥ 0;
[0284] At least one of W and Y>0;
[0285] Z ≥ 0;
[0286] C is in the range of 0≤c<2,
[0287] Wherein V, W, X, Y, Z and C are selected to maintain electrochemical neutrality.
[0288] Ideally, metal M 2 Contains one or more transition metals and is preferably selected from manganese, titanium and zirconium; M 3 Preferably, it is one or more selected from magnesium, calcium, copper, tin, zinc and cobalt; M 4 comprises one or more transition metals, preferably selected from manganese, titanium and zirconium; and M 5 Preferred are one or more selected from aluminum, iron, cobalt, tin, molybdenum, chromium, vanadium, scandium and yttrium.
[0289] Particularly preferred sodium-containing active materials will be nickelate-based materials.
[0290] Sodium-containing active materials having any crystal structure can be used, however, preferably, the structure will be O3 or P2 or a derivative thereof, but, in particular, it is also possible that the sodium-containing active material will contain a mixture of phases, i.e. it will have an inhomogeneous structure consisting of several different crystal forms. For example, the sodium-containing active material will contain compounds having the general formula detailed above in a mixture of O3 and P2 phases. The ratio of O3:P2 phases is preferably 1 to 99:99 to 1.
[0291] The cathode disclosed herein may also include a binder. The binder improves the bonding properties between the sodium-containing active material particles and between the sodium-containing active material particles and the current collector. The binder may be a non-aqueous binder, an aqueous binder, or a combination thereof.
[0292] The non-aqueous binders that may be mentioned herein include, but are not limited to, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, and polyimide.
[0293] The aqueous binder mentioned herein includes but is not limited to a rubber-based binder or a polymer resin binder. The rubber-based binder can be selected from styrene-butadiene rubber, acrylated styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber and combinations thereof.
[0294] The polymer resin binder may be selected from ethylene propylene copolymer, epichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol and combinations thereof.
[0295] Cellulose-based compounds can be used as binders (or in combination with other materials). Examples of suitable cellulose-based materials include, but are not limited to, one or more of carboxymethyl cellulose, hydroxypropyl methylcellulose, methylcellulose or its alkali metal salts. The alkali metal can be Na, K or Li. Based on 100 parts by weight of active material, this cellulose-based compound can be included in an amount of about 0.1 parts by weight to about 20 parts by weight. A specific cellulose-based binder that can be mentioned herein is the sodium salt of carboxymethyl cellulose.
[0296] The anode-free batteries disclosed herein may include a separator positioned between the cathode and anode current collectors. The electrolyte composition according to the present invention has particular utility when used in an anode-free battery including a polyolefin separator.
[0297] In an alternative aspect, the present invention also provides a sodium battery comprising the non-aqueous electrolyte composition defined herein.
[0298] More specifically, the present invention provides a sodium ion battery comprising a negative electrode, a positive electrode and a non-aqueous electrolyte composition as defined herein. Such a sodium ion battery can be used in energy storage devices such as batteries, rechargeable batteries, electrochemical devices and electrochromic devices.
[0299] Ideally, the non-aqueous electrolyte composition defined herein is used in a sodium ion battery employing a carbonaceous material as the active negative (anode) electrode material. Most preferably, the non-aqueous electrolyte composition of the present invention is used with a non-graphitizable carbonaceous anode, preferably a hard carbon anode. BRIEF DESCRIPTION OF THE DRAWINGS
[0301] The present invention will now be described with reference to the following drawings, in which:
[0302] Figure 1a A graph of cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling stability of cells using a control electrolyte composition (sample TEL 66i) in the 3.70 to 1.0 V window.
[0303] Figure 1b A graph of Coulombic efficiency % versus cycle number is shown to illustrate the cycling performance of a cell using a control electrolyte composition (sample TEL 66i).
[0304] Figure 2a A graph showing cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling stability of cells using the electrolyte compositions of the present invention (Samples TEL66j, TEL 66k, TEL 66L, TEL 66m, and TEL 66n) compared to the cycling stability of cells using a control electrolyte composition (Sample TEL 66i).
[0305] Figure 2b A graph of Coulombic efficiency % versus cycle number is shown to illustrate the cycling performance of cells using the electrolyte compositions of the present invention (Samples TEL 66j, TEL 66k, TEL 66L, TEL 66m, and TEL 66n) compared to the cycling performance of cells using a control electrolyte composition (Sample TEL 66i).
[0306] Figure 2c A graph showing the full cell voltage (V) versus cathode discharge capacity (mAh / g) (i.e., voltage-capacity cycling curve) at the 5th cycle for a battery using the electrolyte composition of the present invention (sample TEL 66n) compared to a battery using a control electrolyte composition (sample TEL 66i).
[0307] Figure 3aA graph of cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling stability of a cell using sample TEL 66R compared to the cycling stability of a cell using sample TEL 66o.
[0308] Figure 3b A graph of Coulombic efficiency % versus cycle number is shown to illustrate the cycling performance of a cell using sample TEL 66R compared to the cycling performance of a cell using sample TEL 66o.
[0309] Figure 4a A graph of cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling stability of cells using the electrolyte compositions of the present invention (Samples TEL 66P, TEL 66Q, TEL 66P, TEL 66h, TEL 66Q, TEL 66S, and TEL 66T).
[0310] Figure 4b A graph of Coulombic efficiency % versus cycle number is shown to illustrate the cycling performance of cells using the electrolyte compositions of the present invention (samples TEL 66P, TEL 66Q, TEL 66P, TEL 66h, TEL 66Q, TEL 66S, and TEL 66T).
[0311] Figure 5a A graph of cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling stability of a cell using an electrolyte composition of the present invention (Sample TEL 66d).
[0312] Figure 5b A graph of cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling performance of a cell using an electrolyte composition of the present invention (Sample TEL 66d).
[0313] Figure 6a A graph showing cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling stability of cells using the electrolyte compositions of the present invention (Samples TEL85b, TEL 66U, TEL 85g, TEL 85h, TEL 85i, and TEL 66V) as compared to the cycling stability of cells using a control electrolyte composition (Sample TEL 66i).
[0314] Figure 6b A graph of Coulombic efficiency % versus cycle number is shown to illustrate the cycling performance of cells using the electrolyte compositions of the present invention (Samples TEL 85b, TEL 66U, TEL 85g, TEL 85h, TEL 85i, and TEL 66V) as compared to the cycling performance of cells using a control electrolyte composition (Sample TEL 66i).
[0315] Figure 7a A graph showing cathode discharge capacity (mAh / g) versus cycle number to illustrate the cycling stability of cells (INFC 73, INFC 74, INFC 75, INFC 82, INFC 83, INFC 76, INFC 96 and INFC 97), each of which uses an electrolyte composition of the present invention (sample TEL 66P), but each is constructed with a different type of anode current collector.
[0316] Figure 7b A graph showing coulombic efficiency % versus cycle number is shown to illustrate the cycling performance of cells (INFC 73, INFC 74, INFC 75, INFC 82, INFC 83, INFC 76, INFC 96 and INFC 97), each of which uses an electrolyte composition of the present invention (sample TEL 66P), but each is constructed with a different type of anode current collector.
[0317] Figure 8a A graph of cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling stability of cells using the electrolyte compositions of the present invention (Samples TEL 66W, TEL 66X, TEL 66Y, TEL 66Z, TEL 85, and TEL 85a).
[0318] Figure 8b A graph of Coulombic efficiency % versus cycle number is shown to illustrate the cycling performance of cells using the electrolyte compositions of the present invention (Samples TEL 66W, TEL 66X, TEL 66Y, TEL 66Z, TEL 85, and TEL 85a).
[0319] Figure 9a A graph of cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling stability of cells using the electrolyte compositions of the present invention (Samples TEL 66d, TEL 85e, TEL 85f, and TEL 66P).
[0320] Figure 9b A graph of Coulombic efficiency % versus cycle number is shown to illustrate the cycling performance of cells using the electrolyte compositions of the present invention (Samples TEL 66d, TEL 85e, TEL 85f, and TEL 66P). Example
[0321] The electrolyte composition of the present invention is particularly effective as an electrolyte composition for an anode-less sodium battery. The anode-less sodium battery can be prepared as follows.
[0322] The cathode is formed of a first current collector having a positive active material disposed on a surface of the first current collector.
[0323] The positive electrode active material is a sodium-containing active material, which may or may not be mixed with any type of conductive additive, such as carbon black (to enhance the electronic conductivity of the positive electrode active material) and / or a binder material (water or an organic solvent). The positive electrode active material is then coated on an aluminum (or other metal) current collector using conventional electrode processing techniques, such as those described in WO 2020 / 240209 A1.
[0324] The anode is formed by an additional (second) current collector which is simply a thin metal substrate (e.g. a foil) made of copper, aluminum, stainless steel or any other metal substrate (similar to the current collectors currently commonly used in sodium-ion batteries).
[0325] As shown in the examples, in one embodiment, before the initial first charge cycle of the anode-free sodium battery, the anode current collector does not include any nucleation layer on one or more surfaces of the anode current collector. Therefore, before the initial first charge cycle of the anode-free sodium battery, the anode current collector is pristine.
[0326] As also shown in the Examples, in alternative embodiments, the anode current collector includes one or more nucleation layers formed on one or more surfaces of the anode current collector prior to an initial first charge cycle of the anode-free sodium battery.
[0327] Positive electrode (cathode electrode)
[0328] Fabrication of anode-free sodium batteries using mixed-phase O3 / P2 oxide positive electrode active materials; O3 / P2-A 1±δ M 1 V M 2 W M 3 X M 4 Y M 5 Z O 2-c , which is prepared as described in International Application No. PCT / GB2019 / 051022 (published as WO 2019 / 197812 A1) and U.S. Patent No. 10,550,007.
[0329] Using Malvern 2000 and ethanol were used as dispersants, and the particle size d50 of the positive electrode active material was measured by laser diffraction to be 10±2 μm. The tap density of the positive electrode active material was also >0.96 g / ml.
[0330] The positive (cathode) electrode is then prepared by solvent casting a slurry of active material, conductive carbon, binder and solvent. The conductive carbon used is C65 (Imerys). PVdF copolymer (e.g. W#7500 from Kureha Chemicals) is used as a binder and N-methylpyrrolidone (NMP) is used as a solvent. The slurry is then cast onto a carbon-coated aluminum foil and dried at about 80°C. The electrode film contains the following components, expressed in weight percentage: 89% active material, 5% C65 carbon and 6% V 7500 binder. Alternatively, the electrode film contains the following components, expressed in weight percentage: 92% active material, 4% C65 carbon and 4% W#7500 binder, as discussed below in "Battery Components".
[0331] Preparation of electrolyte
[0332] The electrolyte compositions studied were prepared using the following general procedure: an appropriate amount of the first component (e.g., a solvent for the desired solvent system) and an appropriate amount of the second component (e.g., an additive selected from sulfur-containing compounds / boron-containing compounds / nitrile-containing compounds / phosphorus-containing compounds / surfactants) were weighed out in an argon-filled glove box and added to a brown or transparent glass or metal bottle.
[0333] In order to completely dry the formed solvent system, add Molecular sieve The solvent mixture is allowed to dry for at least 24 hours. Afterwards, the solvent mixture is transferred to another brown or transparent glass bottle containing a magnetic stirring bar while still in the glove box. Then the correct amount of one or more sodium-containing salts are weighed out in an argon-filled glove box and slowly added to the solvent mixture under continuous stirring. The electrolyte mixture is stirred until the sodium-containing salt (multiple sodium-containing salts) are visually determined to have dissolved on the magnetic stirring plate (stirring time will generally be at least 10 minutes, such as 2 hours or 48 hours). The electrolyte composition is then removed from the stirring plate, stored and used in an argon-filled glove box.
[0334] The exact composition of each electrolyte composition investigated is detailed in Table 1 below:
[0335] Table 1
[0336]
[0337]
[0338]
[0339] * indicates an electrolyte composition not according to the present invention.
[0340] Abbreviations used:
[0341] VC = vinylene carbonate, FEC = fluoroethylene carbonate, PCS = 1,3-propylene glycol cyclic sulfate, P123 = poloxamer (Pluronic) P123, TMSB = tris(trimethylsilyl)borate, TOC = trioctyl phosphate, TMSP = tris(trimethylsilyl)phosphite; HTC = 1,3-6-hexanetrionitrile; TMB = trimethoxyboroxine; PST = 1-propylene 1,3 sultone; SUL = sulfolane
[0342] Tetraglyme = tetraethylene glycol dimethyl ether, diglyme = diethylene glycol dimethyl ether, NaBF4 = sodium tetrafluoroborate.
[0343] Please note that in Table 1 above, the weight % of various solvents and / or additives mentioned are relative to the total solvent weight (they do not account for the weight (weights) of the one or more sodium-containing salts). In addition, the salt concentrations in Table 1 are described in terms of weight molar concentration m (moles of solute per kilogram of solvent, mol / kg).
[0344] Battery components
[0345] The anode-free sodium batteries described throughout the examples were fabricated as pouch cells. The cathode contained a mixed phase O3 / P2 layered oxide sodium ion active material mixed with C65 carbon black conductive additive and polyvinylidene fluoride (PVDF) binder (weight ratios such as 89:05:06 or 92:04:04) on carbon-coated aluminum foil.
[0346] The anode is aluminum foil with or without a thin surface carbon coating. Thus, in those embodiments where the anode is made without any active material coating disposed on the current collector, the anode is simply aluminum foil.
[0347] Alternatively, in those embodiments where the anode is made from a nucleation layer disposed on the surface of the current collector, the anode is a 'bare En'Safe 92' substrate, which is an aluminum foil coated with a thin (about 1 μm) carbon primer layer using a doctor blade method and obtained from ARMOR (their En'Safe 92 substrate is 'bare'). series products); or an aluminum foil current collector coated with a carbon black (C65): PVDF (=90:10 weight / weight) layer at a specified GSM.
[0348] After coating the cathode and anode, they are punched out to the desired dimensions.
[0349] The separator used is a general polyolefin separator commonly used in any type of rechargeable lithium-ion or sodium-ion battery, such as 2500. The cathode / separator / anode assembly was placed in a bag inside a glove box and filled with the liquid electrolyte in an amount typical for such lithium-ion or sodium-ion batteries containing a polyolefin separator. These pouch cells were then sealed in a glove box and taken out for battery testing. Throughout the disclosure, pouch cells of two different nominal capacities were used (varying according to the size of the electrode stack): by default, most results are for pouch cells of 6 mAh nominal capacity, and where noted, some results are also for larger scale 0.1 Ah anode-free pouch cells.
[0350] Battery Test
[0351] The cells were tested using a constant current (galvanostatic) cycling technique as follows.
[0352] The battery is cycled between preset voltage limits defined in the examples at a given current density, where the upper cutoff voltage may or may not include a constant voltage step. A commercial battery cycler from MTI Inc. (Richmond, CA, USA) or Maccor (Tulsa, OK, USA) is used. The battery is cycled at 30°C.
[0353]
[0354]
[0355]
[0356]
[0357]
[0358]
[0359]
[0360] Example 1
[0361] Performance of an anode-free sodium cell using 1.5 m NaBF4 (TEL 66i) in 1:1 wt / wt tetraglyme:diglyme.
[0362] The cycling performance was studied with TEL 66i using an anode current collector without a nucleation layer (INFC 59) and an anode current collector with a nucleation layer (INFC 53; INFC 58). In particular, both INFC 53 and INFC 58 used a carbon-containing nucleation layer, i.e., INFC 53 used an "En'safe 92 foil" current collector, and INFC 58 used an 11.3GSM C65 layer on an aluminum foil.
[0363] Figure 1a and 1b The Na plating-stripping process is shown for the three cells after 50-110 cycles when cycled from 3.7 to 1.0 V at a rate of ±C / 5.
[0364] from Figure 1a From the results shown, it can be seen that under the same cycling conditions, INFC 53 and INFC 58 lead to higher capacities in the 3.7-1.0 V window than INFC 59. Specifically, the release capacity of INFC 53 at the 50th cycle is 65 mAh / g, while the release capacity of INFC 59 at the 50th cycle is 0 mAh / g.
[0365] from Figure 1b The results shown show that both INFC 53 and INFC 58 achieve stable Coulombic efficiencies close to 100% throughout the cycling process (e.g., at the 50th cycle mark, the Coulombic efficiency of INFC 53 is about 99% and the Coulombic efficiency of INFC 58 is about 98%), indicating that Na plating and stripping are very stable. Figure 1b As is clear from the results, the Coulombic efficiency of INFC 59 appears to be poor.
[0366] Example 2
[0367] Lower voltage
[0368] The performance of anode-free sodium cells at lower voltages using 1.5 M NaBF4 in 1:1 wt / wt tetraglyme:diglyme with no additives or with one type of additive is shown in Table 2.
[0369] The cycling performance was studied with TEL 66L or TEL 66n at low voltage (ie 3.7 to 1.0 V) using "En'Safe 92 foil" anode.
[0370] Figure 2a and 2b The Na plating-stripping process of two cells (INFC 65; INFC 69) when cycled from 3.7 to 1.0 V at rates of +C / 5, -1C is shown.
[0371] from Figure 2a The results shown show that Figure 1aCompared to the cathode discharge capacity of cell INFC 53 using a control electrolyte composition (TEL 66i) shown, INFC 65 and INFC 69 resulted in similar cathode discharge capacities within the 3.7-1.0 V window. Cells INFC 53, INFC 65 and INFC 69 each used an "En'safe 92 foil" anode current collector.
[0372] Specifically, Figure 1a As shown, the release capacity of INFC 65 and INFC 69 at the 30th cycle was 72.9 mAh / g and 76 mAh / g, respectively, while the release capacity of INFC 53 at the 30th cycle was 73.9 mAh / g. This similar capacity was observed despite the fact that the batteries INFC 65 and INFC 69 were discharged at a faster rate of -1C (1 hour discharge), compared to the slower rate of -C / 5 (5 hour discharge) for the battery INFC 53.
[0373] It is well known that as the battery discharge C rate increases, the expected release capacity decreases. Therefore, the results of INFC 65 and INFC 69 concluded that an improvement in electrochemical performance was observed by adding a boron-containing additive (i.e., TMSB). The results also showed an improvement in the capacity of INFC 69 compared to INFC 65, which can be attributed to the use of a higher amount of TMSB (i.e., 1 wt% vs. 2 wt%).
[0374] from Figure 2b In the results shown, it is also observed that both INFC 65 and INFC 69 achieve a stable Coulombic efficiency close to 100% during the entire cycling process, indicating very stable Na plating and stripping. Figure 1b This is comparable, or if not comparable, slightly improved, compared to the Coulombic efficiency of the INFC 53 shown.
[0375] However, as discussed below, further benefits of using additives according to the present invention are seen at higher voltages.
[0376] Higher voltage
[0377] The performance of anode-free sodium cells at higher voltages using 1.5 m NaBF4 in 1:1 wt / wt tetraglyme: diglyme with no additives or with one type of additive is shown in Table 2. The voltage curve increases from the 3.7-1.0 V window to the 4.0-1.0 V window.
[0378] Figure 2a and 2bThe Na plating-stripping process of five cells using electrolyte compositions according to the present invention (i.e., INFC 62; INFC 64; INFC 67; INFC 61; and INFC 60) when cycled from 4.0 to 1.0 V is shown.
[0379] Also shown are the results for two batteries not according to the invention (ie, INFC 57; and INFC 63) when cycled from 4.0 to 1.0 V.
[0380] from Figure 2a The results shown show that each of INFC 62; INFC 64; INFC 67; INFC 61; and INFC 60 resulted in higher capacity in the 4.0-1.0 V window than INFC 57 and INFC 63, which either used no additive (INFC 57) or did not use an additive according to the present invention (INFC 63).
[0381] The cells with borate-containing additives (INFC 62; INFC 64; and INFC 67) showed greater capacity performance than the cells with sulfur-containing additives (INFC 60) or surfactants (INFC 61). The cells with sulfur-containing additives (INFC 60) also showed greater capacity performance than the cells with surfactants (INFC 61).
[0382] Specifically, the release capacity of each of INFC 62, INFC 64, INFC 67, INFC 61, and INFC 60 at the 20th cycle was 95 mAh / g, 92.2 mAh / g, 88.9 mAh / g, 29.2 mAh / g, and 45.4 mAh / g, respectively.
[0383] The cycling performance of INFC 57 and INFC 63 at 4-1 V was very poor compared to each of INFC 62; INFC 64; INFC 67; INFC 61; and INFC 60, with both batteries essentially failing to pass 5 cycles.
[0384] Figure 2b It also provides an indication of how the additives of the invention affect performance.
[0385] It can be seen that the first cycle efficiency (FCE) of the cells in which the electrolyte composition contains a borate-containing or surfactant-containing additive is significantly higher than that of the control samples: in particular, the FCEs of INFC 62, INFC 64, INFC 67 and INFC 61 are 87.2%, 91.3%, 91% and 70.9%, and these FCE values are higher than those of INFC 57 without additive (64%) or INFC 63 containing an additive not according to the present invention, i.e., a FEC additive (29.8%).
[0386] Although the FCE of INFC 60 containing sulfur-containing additives (i.e. PCS) is very low (9.7%), the reference Figure 2a , and the subsequent increase in capacity and stable cycling point indicates a different mechanism for PCS to act as a film-forming additive.
[0387] Clearly, if the electrolyte contains 2 wt% PCS as the only additive, the decomposition of PCS first leads to a lower FCE, but the decomposition products then appropriately modify the anode current collector substrate, thereby then leading to more stable sodium plating / stripping in subsequent cycles. Therefore, this data indicates a difference in the mechanisms of the additives studied, and these results were previously unanticipated. Furthermore, this may explain the higher capacity observed for the PCS-based electrolyte.
[0388] Figure 2c The cycle performance of the anode-free sodium battery using the electrolyte composition of the present invention is further shown. More specifically, Figure 2c A graph showing the full cell voltage (V) versus cathode discharge capacity (mAh / g) (i.e., voltage-capacity cycling curve) at cycle 5 for cells using an electrolyte composition of the present invention (sample TEL 66n) compared to cells using a control electrolyte composition (sample TEL 66i). Specifically, cells INFC 69 and INFC 67 using TEL 66n were compared to cells INFC 53 and INFC 57 using TEL 66i.
[0389] It can be seen that when batteries INFC 53 and INFC 69 are cycled within the 3.7-1V window (i.e., at a lower voltage), battery INFC 69 provides substantially the same capacity as battery INFC 53. In contrast, when batteries INFC 57 and INFC 67 are cycled within the 4.0-1V window (i.e., at a higher voltage), battery INFC 67 provides significantly greater capacity than battery INFC 57.
[0390] More specifically, as the battery INFC 57 was cycled to higher voltages, it gradually caused more electrolyte oxidation, and after two additional cycles, the INFC 57 refused to charge to 4V to complete the charge. Figure 2c It is further shown that after 7 hours of charging cycling at a C rate of C / 5, battery INFC 57 reaches a cell voltage of 3.2V at the 5th cycle. Those skilled in the art will appreciate that under these conditions, a higher cell voltage (e.g., 4V) should have been achieved before 5 hours (by) / before. Instead, the data indicates that continued electrolyte oxidation during cycling renders the control electrolyte unusable at higher voltages.
[0391] Advantageously, for the battery INFC 67 using the electrolyte composition of the present invention (sample TEL 66n), the battery can be charged to about 4 V at cycle 5. Thus, this data demonstrates Applicants' understanding that TMSB can impart surprising oxidative stability to glyme-based electrolytes, particularly when used in anode-free sodium-ion batteries.
[0392] Example 3
[0393] The performance of an anode-free sodium cell with two types of additives using 1.5 m NaBF4 in 1:1 weight / weight tetraglyme: diglyme at higher voltages was tested in a cell having a voltage curve of 4.0-1.0 V. More specifically, after having established the behavior of the electrolyte composition of the invention comprising one additive in previous experiments, this experiment determined a surprising synergistic effect by using the electrolyte composition of the invention comprising two additives.
[0394] Figure 3a and 3b The Na plating-stripping process is shown for four cells (INFC 72, INFC 92, FPC220215 and FPC220218) using two different types of additives according to the invention, namely a combination of a boron-containing additive (TMSB) and a surfactant (P-123) (sample TEL 66R).
[0395] Figure 3a and 3b Also shown is the Na plating-stripping method of a cell INFC 68 using a combination of one type of additive according to the invention, namely a boron-containing additive (TMSB), and an additive not according to the invention, namely a carbonate-containing additive (VC) (sample TEL 66o).
[0396] from Figure 3aThe results shown show that each of INFC 72, INFC 92, and FPC220218 results in a higher capacity in the 4.0-1.0V window compared to INFC 68, which uses a combination of one type of additive according to the present invention and one additive not according to the present invention. Specifically, each of INFC 72, INFC 92, FPC220218, and INFC 68 has a release capacity of 101 mAh / g, 104.1 mAh / g, 109.6 mAh / g, and 46.5 mAh / g at the 4th cycle, respectively. This shows that the choice of additives is important for performance, and different combinations of additives result in different electrochemical performance, which is unpredictable.
[0397] Therefore, it is preferred that the nonaqueous electrolyte composition according to the present invention is substantially free of one or more carbonate-based compounds, such as vinylene carbonate.
[0398] Furthermore, cells INFC 72, INFC 92, and FPC220218 each exhibited higher or similar capacity performance compared to cells INFC 62, INFC 64, and INFC 67 using the boron-containing additive (TMSB) alone or cell INFC 61 using the surfactant (P123) alone.
[0399] Specifically, the release capacity of each of INFC 72, INFC 92 and FPC220218 at the 20th cycle was 92.3 mAh / g, 92.5 mAh / g and 102.3 mAh / g, respectively, compared with 95 mAh / g, 92.2 mAh / g, 88.9 mAh / g, 29.2 mAh / g and 45.4 mAh / g, respectively, for each of INFC 62, INFC 64, INFC 67, INFC 61 and INFC 60 at the 20th cycle.
[0400] This synergistic performance is highly unexpected and demonstrates once again that different combinations of additives lead to different electrochemical performances, which are unpredictable.
[0401] from Figure 3b The results shown show that each of INFC 72, INFC 92, and FPC220218 achieves a stable Coulombic efficiency close to 100% throughout the cycling process (about 92-96% at the 20th cycle), indicating that Na plating and stripping are very stable. In contrast, for cell INFC 68, a Coulombic efficiency of 36.9% was observed at the 4th cycle.
[0402] As also verified by battery cycling of FPC220215 using sample TEL 66R, good cycling is seen even under different cycling conditions in different voltage windows (eg, stable cycling at 3.7-1 V is seen with a capacity retention of 78.4% over 110 cycles).
[0403] Example 4
[0404] Lower voltage
[0405] The performance of anode-free sodium cells at lower voltages using 1.5 m NaBF4 in 1:1 wt / wt tetraglyme: diglyme using three types of additives is shown in Table 2. The cells were tested within the voltage curve of 3.7-1.0 V.
[0406] Figure 4a and 4b The Na plating-stripping process of the cell FPC220213 using three different types of additives according to the present invention, namely a combination of a boron-containing additive (TMSB) with a sulfur-containing additive (PCS) and a surfactant (P123), namely sample TEL 66P, is shown.
[0407] Figure 4a and 4b Also shown in the figure are the results for a cell (FPC220214) using a combination of two types of additives according to the invention, namely a boron-containing additive (TMSB) and a surfactant (P123) and an additive not according to the invention, namely a carbonate-containing additive (FEC). This is sample TEL 66Q.
[0408] from Figure 4a The results shown show that under the same cycling conditions, FPC220213 leads to higher capacity than FPC220214 in the window of 3.7-1.0 V. Specifically, the release capacity of each of FPC220213 and FPC220214 at the 110th cycle is 76.9 mAh / g and 66.9 mAh / g, respectively.
[0409] Higher voltage
[0410] The performance of the anode-free sodium battery with additives at higher voltages using 1.5 m NaBF4 in 1:1 wt / wt tetraglyme: diglyme is shown in Table 2. The voltage curve increases from the 3.7-1.0 V window to the 4.0-1.0 V window.
[0411] Figure 4a and 4bThe Na plating-stripping process of the FPC220216 cell using sample TEL 66P in the 4.0-1.0 V window and the FPC220217 cell also using sample TEL 66Q in the 4.0-1.0 V window is shown.
[0412] from Figure 4a and 4b The results shown show that, under the same cycling conditions, FPC220216 leads to higher capacity than FPC220217 in the 4.0-1.0 V window: after the 20th cycle, the former releases a specific capacity of 103.3 mAh / g, while the latter has a specific capacity of only 79.7 mAh / g.
[0413] FPC220216 using TEL 66P also showed higher capacity performance than cells with boron-containing additives alone (INFC 62; INFC 64; and INFC 67), sulfur-containing additives alone (INFC 60), or surfactants alone (INFC 61), as discussed in Example 2 above (see Figure 2a ).
[0414] Specifically, each of INFC 60, INFC 61, INFC 62, INFC 64, and INFC 67 had a release capacity of 45.3 mAh / g, 29.2 mAh / g, 95 mAh / g, 92.2 mAh / g, and 88.9 mAh / g, respectively, at cycle 20. These capacity values are lower, sometimes significantly lower, than the specific capacity (103.3 mAh / g) seen for battery FPC220216 after cycle 20, indicating the surprising beneficial effect of using TEL 66P.
[0415] Anode-free cells utilizing a glyme-based electrolyte containing three additives according to the present invention also outperform those anode-free cells utilizing a glyme-based electrolyte containing three additives, one of which is not an additive according to the present invention.
[0416] exist Figure 4a and Figure 4b Focusing on anode-free batteries of similar capacity (about 6 mAh), it can be seen that the cycling stability of INFC 70 (TEL 66P), INFC 78 (TEL 66S) and INFC 79 (TEL 66T) is better than that of INFC 45 (TEL 66h) and INFC 71 (TEL 66Q).
[0417] Specifically, the discharge capacity of various batteries at the 20th cycle is:
[0418] INFC 70 (TEL 66P) = 90.8 mAh / g
[0419] INFC 78 (TEL 66S) = 93.1 mAh / g
[0420] INFC 79 (TEL 66T) = 90.2 mAh / g
[0421] INFC 45 (TEL 66h) = 0.02 mAh / g
[0422] INFC 71 (TEL 66Q) = 83.1 mAh / g
[0423] Therefore, it is preferred that the nonaqueous electrolyte composition according to the present invention is substantially free of one or more carbonate-based compounds, such as fluoroethylene carbonate.
[0424] Example 5
[0425] High voltage; Effects of three additives; Long-term cycling
[0426] The long-term cycling performance of anode-free sodium batteries (INFC 16, INFC 17, INFC 19 and INFC 20) over 200 cycles from 4.0 V to 1 V was studied, wherein the anode-free sodium batteries used an electrolyte composition containing 1.5 m NaBF4 in 1:1 wt / wt tetraethylene glycol dimethyl ether: diethylene glycol dimethyl ether and a mixture of 2 wt% PCS, 1 wt% P123 and 1 wt% TMSB (sample TEL 66d).
[0427] INFC 16, INFC 17, INFC 19, and INFC 20 using TEL 66d were all cycled from 4.0-1.0V, but at slightly different cycling rates:
[0428] INFC 16 and INFC 17: first two cycles at C / 10, followed by 200 cycles at +C / 5, -1C.
[0429] INFC 19: first two cycles at +C / 10, -1C, followed by 200 cycles at +C / 5, -1C.
[0430] INFC 20: first five cycles at +C / 10, -1C at 3-1V, followed by two cycles at +C / 10, -1C, and then finally 200 cycles at +C / 5, -1C.
[0431] from Figure 5aIt can be seen that after 200 cycles at +C / 5, -1C, all four batteries show good capacity retention: relative to the first cycle at +C / 5, -1C, the capacity retention of each battery is INFC 16 (50.4%), INFC 17 (49.9%), INFC 19 (33.3%) and INFC 20 (31.9%).
[0432] like Figure 5b As shown, the stable Coulombic efficiency of all cells is about 100% throughout the +C / 5, -1C cycle life: for example, the Coulombic efficiency of each cell at the 200th cycle at +C / 5, -1C is INFC 16 (98.5%), INFC 17 (100.5%; the efficiency at the 199th cycle is 97.6%), INFC 19 (95.2%; the efficiency at the 199th cycle is 101.5%), and INFC 20 (97.2%).
[0433] These Coulombic efficiency values after 200 cycles are significantly higher than those obtained for the battery INFC 57 cycled with the control electrolyte composition (sample TEL66i). Figure 2a As shown, the coulombic efficiency of the battery INFC 57 at the 5th cycle (3rd +C / 5, -1C cycle) is only 16.99% (see Figure 2c The corresponding cycle curve of the battery in ).
[0434] As discussed above in Example 2, Applicants understand that the low Coulombic efficiency values for cells cycled with the control electrolyte composition (Sample TEL 66i) are a result of poor oxidative stability when cycled at high voltages. However, this poor oxidative stability is not observed for anode-free sodium cells cycled at higher voltages with Sample TEL66d, as shown in this long-term cycling experiment.
[0435] Example 6
[0436] The cycling performance of an anode-free sodium battery at +C / 5, -1C rates at 4-1V was studied using an electrolyte composition containing 1.5 m NaBF4 in 1:1 weight / weight tetraethylene glycol dimethyl ether: diethylene glycol dimethyl ether and additives not used in any of the previous experiments. This composition is detailed in Experiments 6A-6F of Table 2.
[0437] Figure 6a / 6b shows a graph of cathode discharge capacity (mAh / g) / % coulombic efficiency versus cycle number for cells using the electrolyte composition of the present invention (samples TEL 85b, TEL 66U, TEL 85g, TEL 85h, TEL 85i and TEL 66V) compared to a cell using a control electrolyte composition (sample TEL 66i). Taking each sample in turn:
[0438] TEL 85b (containing boroxine):
[0439] Cell INFC 93 was cycled with TEL 85b, and the cycling performance was significantly more stable than that of cell INFC 57 cycled with control electrolyte composition TEL 66i. Surprisingly, the FCE of INFC 93 was lower than that of INFC 57, but the subsequent coulombic efficiency was about 100%, which was significantly higher than the efficiency of INFC 57 (e.g., the coulombic efficiency of INFC 93 at the 5th cycle was 97.1%, compared to only 16.99% for INFC 57).
[0440] TEL 66U (containing phosphite)
[0441] Cell INFC 100 cycled with TEL 66U showed worse cycling performance than cell INFC 93 cycled with TEL 85b, but significantly better than cell INFC 57 cycled with control electrolyte composition TEL 66i: for example, the 5th cycle capacity of INFC 100 was 41.2 mAh / g, significantly higher than the 21.4 mAh / g released by INFC 57.
[0442] TEL85g (containing sultone)
[0443] Cell INFC 105 cycled with TEL 85g showed better cycling performance than cell INFC 57 cycled with control electrolyte composition TEL 66i: for example, the 5th cycle capacity of INFC 105 was 72.6 mAh / g, significantly higher than the 21.4 mAh / g released by INFC 57.
[0444] TEL 85h (containing sulfolane)
[0445] Cell INFC 106 cycled with TEL 85h has very similar cycling performance to cell INFC 105 cycled with TEL 85g, but has improved indicators in terms of cycling stability (5th cycle capacity of INFC 106 is 92.1 mAh / g, while it is 72.6 mAh / g for INFC 105) and subsequent stable coulombic efficiency (5th cycle coulombic efficiency of INFC 106 is 97.2%, while it is only 51.8% for INFC 105), with similar FCE (77.3% for INFC 106 vs. 80.7% for INFC 105). Cell INFC 106 shows much better performance than cell INFC 57 cycled with control electrolyte composition TEL66i.
[0446] TEL 85i and TEL 66V (with nitrile)
[0447] The cells INFC 107 and INFC 81 were cycled with the nitrile-containing additive 1,3,6-hexanetricarbonitrile. In particular, the cell INFC 107 was cycled with TEL 85i and the cell INFC 81 was cycled with TEL 66V.
[0448] The cycling performance of INFC 107 using TEL 85i shows improvement over the cell INFC 57 cycled with the control electrolyte composition TEL 66i: for example, the 5th cycle capacity of INFC 107 is 73.2 mAh / g, significantly higher than the 21.4 mAh / g released by INFC 57.
[0449] Similarly, the cycling performance of INFC 81 using TEL 66v showed improvement over the battery INFC 57 cycled with the control electrolyte composition TEL66i; for example, the 5th cycle capacity of INFC 81 was 53.3 mAh / g, significantly higher than the 21.4 mAh / g released by INFC 57.
[0450] Example 7
[0451] This experiment studies the cycling performance of anode-free sodium batteries composed of different types of anode current collectors / substrates when using an electrolyte composition according to the present invention (TEL 66P). This battery is cycled at 3.7-1.0V at +C / 5, -1C, and the experiments are represented in Table 2 as experiments 7A to 7H.
[0452] Figure 7a and 7bA graph showing cathode discharge capacity (mAh / g) / % coulombic efficiency versus cycle number to illustrate the cycling stability of cells (INFC 73, INFC 74, INFC 75, INFC 82, INFC 83, INFC 76, INFC 96 and INFC 97), each using an electrolyte composition of the invention (sample TEL 66P) but each consisting of a different type of anode current collector / substrate.
[0453] Original current collector
[0454] Three different types of pristine anode current collectors were investigated:
[0455] INFC 73 uses original aluminum foil as substrate;
[0456] INFC 74 uses original copper mesh foil (obtained from Dexmet Cu25); and
[0457] INFC 75 uses virgin aluminum mesh foil (obtained from Dexmet Al25).
[0458] from Figure 7a The results shown clearly show that INFC 73 exhibits the worst cycling performance; very unstable cycling - a sign of an unreliable sodium plating / stripping process.
[0459] INFC 75 performs significantly better than INFC 73 in all indicators: INFC 75 shows more stable cycling (40 mAh / g at the 80th cycle, or 74.2% capacity retention relative to the initial cycle) with high stable Coulombic efficiency (e.g., 101.6% at the 80th cycle).
[0460] The metrics obtained for INFC 74 are even better than those for INFC 75: compared to INFC 75, INFC 74 exhibits higher capacity with better capacity retention after 80 cycles (58.6 mAh / g and 85.5%, respectively), as well as a similarly high and stable Coulombic efficiency (99.3% Coulombic efficiency for INFC 75 at the 80th cycle).
[0461] This experiment shows that different anode current collectors can be used for anode-free sodium batteries when using the electrolyte composition according to the present invention.
[0462] Current collector including a nucleation layer
[0463] As shown in Table 3, five different types of anode current collectors including one or more carbon-containing nucleation layers were investigated:
[0464] INFC 82, INFC 83 and INFC 76 each used a carbon-containing nucleation layer on aluminum foil;
[0465] INFC 97 uses a carbon-containing nucleation layer on an aluminum mesh; and
[0466] • INFC 96 uses two carbon-containing nucleation layers on aluminum foil (ie the applicant applies a carbon (C65) nucleation layer to the En'Safe 92 current collector, which itself consists of an aluminum foil containing a carbon nucleation layer).
[0467] The carbon-containing nucleation layer was prepared by mixing carbon black (C65) as active material and PVDF binder (weight ratio of C65:PVDF 90:10). Then a slurry was obtained by adding NMP solvent and mixing. The slurry was then doctor-coated onto aluminum foil / aluminum mesh / En'Safe 92 current collector foil as shown. The GSM (loaded with only C65) of each cell substrate was as shown. Figure 7a and Figure 7b shown.
[0468] The cycling performance of cells using these coated substrates, in particular INFC 82, INFC 83, INFC 76, INFC 96 and INFC 97, are compared in Table 3 below:
[0469] Table 3
[0470]
[0471] From the results in Table 3, it can be seen that cells cycled with TEL 66P show good cycling performance under various coating GSMs on a range of different types of current collectors including one or more carbon-containing nucleation layers.
[0472] For batteries INFC 82, 83 and 76 using current collectors made of aluminum foil, as the GSM of the carbon nucleation layer or layers increases, the initial capacity and FCE decrease, but the cycling stability increases.
[0473] INFC 96 using 0.7GSM C65 coating on En’Safe 92 foil also showed very good performance indicators in terms of release capacity, FCE and cycling stability.
[0474] As also shown by the performance of INFC 97 relative to that of INFC 75, it can be seen that one or more carbon-containing nucleation layers (C65) on the aluminum mesh enhance the cycling performance: INFC 75 releases 56.3 mAh / g (FCE = 61.4%) in the first cycle, which is significantly lower than the capacity released by INFC 97.
[0475] Example 8
[0476] Effect of Higher Weight % of Additives
[0477] The performance of anode-free sodium cells at higher voltages using 1.5 m NaBF4 in 1:1 wt / wt tetraglyme: diglyme with higher wt% of the three types of additives is shown in Table 2. The cells were tested within the voltage curve of 4.0-1.0 v.
[0478] Figure 8a / 8b shows a graph of cathode discharge capacity (mAh / g) / % coulombic efficiency versus cycle number for cells using the electrolyte composition of the present invention (samples TEL 66W, TEL 66Y, TEL 66Z, TEL85 and TEL 85a).
[0479] Higher weight % sulfur (PCS)
[0480] Cell INFC 84 was cycled with 7 wt % PCS and cell INFC 85 was cycled with 15 wt % PCS.
[0481] like Figure 8a and 8b As shown, at this high PCS wt %, the performance is quite poor and both cells fail rapidly within a few cycles.
[0482] Particularly striking is cell INFC 85, which does not show any reversible capacity, illustrating the negative impact on performance when the electrolyte composition contains 15 wt% PCS.
[0483] Higher wt% boron (TMSB)
[0484] Cell INFC 91 was cycled with 8.5 wt % TMSB and cell INFC 90 was cycled with 15 wt % TMSB.
[0485] like Figure 8a and 8bAs shown, both INFC 91 and INFC 90 released high first discharge capacities (106.2 mAh / g and 105.2 mAh / g, respectively) at high FCE values (91.1% and 90.3%, respectively) and had good cycling stability after 50 cycles (capacity retention rates were 80.5% and 80.6%, respectively, after 30 cycles).
[0486] Higher surfactant wt% (P123)
[0487] Cell INFC 88 was cycled with 7.5 wt % P123 and cell INFC 89 was cycled with 15 wt % P123.
[0488] like Figure 8a and 8b As shown, battery INFC 88 resulted in a capacity of 100.6 mAh / g in the first cycle with a FCE of 76.1%. When the amount of P123 was increased to 15 wt%, battery INFC 89 showed a reduced first cycle capacity of 68.9 mAh / g at a lower FCE of 49.2%.
[0489] in conclusion
[0490] Compared to the cell INFC 57 using the control electrolyte composition (TEL 66i), under comparable conditions, the following performance benefits in terms of higher discharge capacity and coulombic efficiency (as shown in brackets) were observed at the 5th cycle:
[0491] INFC 57: 21.4 mAh / g (16.99%)
[0492] INFC 91: 102.7 mAh / g (97.2%)
[0493] INFC 90: 101.6 mAh / g (97.3%)
[0494] INFC 88: 95.9 mAh / g (97.3%)
[0495] INFC 89: 71.1 mAh.g (50.8%)
[0496] Therefore, good cycling performance of anode-free sodium batteries can still be observed at higher additive weight %.
[0497] Example 9
[0498] Effect of Alternating Voltage Window
[0499] The performance of anode-free sodium cells at higher voltages using 1.5 m NaBF4 in 1:1 wt / wt tetraglyme:diglyme with higher wt % of the three types of additives is shown in Table 2. The cells were tested in the voltage profiles shown in Table 2 and discussed below.
[0500] Figure 9a / 9b shows a graph of cathode discharge capacity (mAh / g) / % coulombic efficiency versus cycle number for cells using the electrolyte composition of the present invention (samples TEL 66d, TEL 85e, TEL 85f and TEL66P).
[0501] 4.05-1V
[0502] The cells were cycled using TEL 66d (cell INFC 101), TEL 85e (INFC 102), or TEL 85f (INFC 103) over a wide voltage window of 4.05-1 V. The data for the 10th cycle are shown below:
[0503] INFC 101: 89.7 mAh / h (Coulombic efficiency = 101.6%; Capacity retention rate = ~100%)
[0504] INFC 102: 89.4 mAh / g (Coulombic efficiency = 95.6%; Capacity retention rate = ~100%)
[0505] INFC 103: 100mAh / h (Coulomb efficiency = 95.5%; capacity retention rate = 95.2%)
[0506] The capacity retention was calculated relative to the first cycle of the corresponding batteries.
[0507] From this data and Figure 9a and 9b As can be seen, these batteries show good cycling stability and performance under these conditions.
[0508] 4-2.5V
[0509] The FPC220245 battery was cycled within the 4-2.5V window using the TEL 66P. The data for the 10th cycle (relative to the first cycle) is shown below:
[0510] FPC220245: 84.6 mAh / g (Coulombic efficiency = 98.9%; capacity retention rate = 94%)
[0511] The capacity retention was calculated relative to the first cycle of the corresponding batteries.
[0512] These examples demonstrate that anode-free sodium batteries using the electrolyte composition of the present invention can show good cycling performance, stable cycling within different voltage windows, and demonstrate multifunctionality.
Claims
1. A non-aqueous electrolyte composition comprising: one or more sodium-containing salts; and a solvent system comprising: a first component comprising one or more glyme-based solvents; and a second component comprising one or more additives selected from the group consisting of: Sulfur-containing compounds in an amount not greater than about 10% by weight of the solvent system; a boron-containing compound in an amount not greater than about 20% by weight of the solvent system; a nitrile-containing compound in an amount not greater than about 10% by weight of the solvent system; a phosphorus-containing compound in an amount not greater than about 10% by weight of the solvent system; A surfactant in an amount no greater than about 20% by weight of the solvent system; and The total amount of the one or more additives does not exceed about 20 wt % based on the weight of the solvent system.
2. The nonaqueous electrolyte composition of claim 1 , wherein the second component comprises two or more additives, the two or more additives comprising a boron-containing compound in an amount of >0 wt % to <20 wt % of the solvent system and a surfactant in an amount of >0 wt % to <20 wt % of the solvent system, and wherein the total amount of the two or more additives does not exceed about 20 wt % based on the weight of the solvent system.
3. The nonaqueous electrolyte composition of claim 1 , wherein the second component comprises three or more additives, the three or more additives comprising a sulfur-containing compound in an amount of >0 wt % to <10 wt % of the solvent system, a boron-containing compound in an amount of >0 wt % to <20 wt % of the solvent system, and a surfactant in an amount of >0 wt % to <20 wt % of the solvent system, and wherein the total amount of the three or more additives does not exceed about 20 wt % based on the weight of the solvent system. 4 . The nonaqueous electrolyte composition according to claim 1 , wherein the sulfur-containing compound is selected from the group consisting of a sulfone-containing compound, a sulfuric acid ester-containing compound, and a sulfonic acid ester-containing compound.
5. The nonaqueous electrolyte composition according to claim 4, wherein the sulfur-containing compound is selected from the group consisting of sulfolane, 3-methylsulfolane, trimethyl sulfone, methyl phenyl sulfone, 1,3-propylene glycol cyclic sulfate (PCS), 1,5,2,4-dioxadithiolane 2,2,4,4-tetraoxide, 1,3,2-dioxathiolane 2,2-dioxide, 1-propylene 1,3-sultone and 1,3-propane sultone. 6 . The nonaqueous electrolyte composition according to claim 4 , wherein the sulfur-containing compound comprises 1,3-propylene glycol cyclic sulfate (PCS). 7 . The nonaqueous electrolyte composition according to claim 1 , wherein the boron-containing compound is selected from a borate-containing compound and a boroxine-containing compound.
8. The nonaqueous electrolyte composition according to claim 7, wherein the boron-containing compound is selected from tris(trimethylsilyl)borate (TMSB), tris(2,2,2-trifluoroethyl)borate, trimethyl borate, triethyl borate, trimethoxyboroxine and trimethylboroxine. 9 . The nonaqueous electrolyte composition according to claim 1 , wherein the nitrile-containing compound comprises 1,3-6-hexanetricarbonitrile. 10 . The nonaqueous electrolyte composition of claim 1 , wherein the phosphorus-containing compound comprises tris(trimethylsilyl)phosphite (TMSP).
11. The nonaqueous electrolyte composition according to any one of claims 1 to 10, wherein the surfactant is selected from anionic surfactants, cationic surfactants, nonionic (hydrophilic) surfactants and amphoteric (zwitterionic) surfactants.
12. The nonaqueous electrolyte composition of claim 11, wherein the surfactant comprises at least one nonionic block copolymer surfactant.
13. The non-aqueous electrolyte composition according to any one of claims 1 to 12, wherein the first component comprises tetraglyme and diglyme, preferably tetraglyme and diglyme in a weight ratio of 1:
1.
14. An anode-free sodium battery, comprising: a cathode comprising one or more sodium-containing active materials; Anode current collector; a separator located between the cathode and anode current collectors; and The nonaqueous electrolyte composition according to any one of claims 1 to 13.
15. The anode-free sodium battery according to claim 14, wherein the anode current collector comprises one or more carbon-containing nucleation layers formed on the surface of the anode current collector prior to an initial first charge cycle of the anode-free sodium battery.
16. An anode-free sodium battery according to any one of claims 14 to 15, wherein the one or more sodium-containing active materials are selected from sodium transition metal oxides, polyanionic compounds and Prussian blue compounds (including analogs thereof).
17. A device comprising one or more anode-free sodium batteries according to any one of claims 14 to 16.
18. A method of operating an anode-free sodium battery according to any one of claims 14 to 15.
19. The method of claim 18, wherein the anode-free sodium battery has a charge cutoff voltage of 4.0 V or higher.
20. Use of the non-aqueous electrolyte composition according to any one of claims 1 to 13 in an anode-free sodium battery.
